Heat-curable composition, adhesive sheet, printed wiring board, and electronic appliance
Patent Information
- Application Number
- JP2022161154
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-10-05
- Publication Date
- 2024-12-19
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing polyimide-based compositions face issues with separation between members due to insufficient alkali resistance during plating processes, ion migration leading to short circuits after heat cycles, and inadequate lamination properties with LCP substrates, compromising insulation reliability and adhesion.
A thermosetting composition comprising a polyimide resin with phenolic hydroxyl groups and a cross-linking agent, featuring a specific molecular structure that forms a strong cross-linked network, enhancing alkali resistance, acid resistance, and lamination properties with LCP substrates, while maintaining insulation reliability.
The composition achieves excellent plating solution resistance, alkali resistance, acid resistance, and insulation reliability, with improved lamination properties to LCP substrates, ensuring stability under extreme temperature changes.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to a thermosetting composition containing a polyimide resin, an adhesive sheet made of the thermosetting composition, and a printed wiring board and an electronic device formed using the adhesive sheet. [Background technology]
[0002] Polyimide resins have excellent heat resistance and chemical resistance and are therefore widely used in a wide range of fields, including electrical insulation and electronics. For example, Patent Document 1 discloses a method of forming a coating film by inkjet coating a thermosetting ink composition containing an amide acid having a specific structure and curing the resulting coating to obtain a polyimide film. Patent Document 2 also discloses a polyimide adhesive containing a terminally modified polyimide, a crosslinking agent, and an organic solvent. This terminally modified polyimide uses a reaction product of a primary monoamine and an acid anhydride-terminated polyimide, which is a reaction product of a monomer group including an aromatic tetracarboxylic acid anhydride and a dimer diamine.
[0003] Patent Document 3 discloses a polyimide-based adhesive composition containing a polyimide resin obtained by reacting aromatic tetracarboxylic acids with diamines containing a specific amount of dimer diamine, a thermosetting resin, a flame retardant, and an organic solvent. Patent Document 4 also discloses a polyimide-based adhesive composition using a polyimide resin obtained by further chain-extending the polyimide resin with diamines containing a specific amount of dimer diamine. Patent Document 4 discloses a resin film exhibiting specific dielectric properties, containing a polyimide obtained by reacting a tetracarboxylic anhydride component with a diamine component having a dimer structure. Patent Document 5 discloses a resin composition containing a polyimide resin containing aliphatic, alicyclic, and / or aromatic tetracarboxylic acid residues and diamine residues containing dimer diamine, an epoxy resin, and a curing agent capable of curing epoxy groups. Patent Document 6 discloses a polyamic acid resin that is a reaction product of an aminophenol compound, an aliphatic diamino compound, a tetrabasic acid dianhydride, and an aromatic diamino compound, and is an imidized product of the polyamic acid resin having amino groups at both ends. Also disclosed is a resin composition containing a terminally modified polyimide resin obtained using this polyimide resin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Laid-Open No. 2013-032501 [Patent Document 2] Japanese Patent Application Laid-Open No. 2016-191049 [Patent Document 3] Japanese Patent Application Laid-Open No. 2013-199645 [Patent Document 4] Japanese Patent Publication No. 2020-056011 [Patent Document 5] Japanese Patent Application Laid-Open No. 2015-117278 [Patent Document 6] International Publication No. 2020 / 189354 Summary of the Invention [Problem to be solved by the invention]
[0005] When exposed to alkaline or acidic solutions during the plating process in the manufacture of electronic components, there is a problem that lifting or peeling easily occurs between components. For example, the amic acid-containing thermosetting ink composition disclosed in Patent Document 1 has a problem of poor storage stability due to the use of polyamic acid, which is a polyimide precursor. Furthermore, the ink composition uses a polyamic acid with a high acid value, which results in insufficient plating solution resistance. Furthermore, the polyimide-based adhesives disclosed in Patent Documents 2 and 3 have a problem of insufficient alkali resistance, which results in the adhesive layer easily peeling when exposed to alkaline aqueous solutions.
[0006] Meanwhile, with the recent widespread use of electronic devices such as smartphones and tablet terminals, reliability over a wide temperature range is required. High insulation reliability is particularly required against extreme temperature changes (hereinafter, insulation reliability after heat cycle testing). For example, the polyimide-based adhesive disclosed in Patent Document 2 is prone to ion migration and short circuits when a voltage is applied after a heat cycle test, resulting in problems with insulation reliability. The polyimide-containing resin film disclosed in Patent Document 4 and the resin composition disclosed in Patent Document 5 also have problems with insulation reliability after a heat cycle test.
[0007] Furthermore, with the recent advances in high-speed and high-capacity wireless communications, liquid crystal polymer (LCP) substrates with low dielectric properties have been attracting attention, and there is a market demand for materials that are compatible with LCP substrates. However, LCP substrates have a problem in that they are prone to temporary adhesion defects during the lamination process in which they are temporarily attached to a thermosetting sheet. For example, the polyimide resin composition disclosed in Patent Document 6 has a problem in that it lacks laminability with LCP substrates.
[0008] The present invention has been made in view of the above-mentioned background, and aims to provide a thermosetting composition that has excellent lamination properties to LCP substrates and that, upon curing, gives a cured product that has excellent plating solution resistance (alkali resistance and acid resistance) and excellent insulation reliability after a heat cycle test; an adhesive sheet; and a printed wiring board and electronic device formed using this adhesive sheet. [Means for solving the problem]
[0009] As a result of extensive research, the present inventors have found that the problems of the present invention can be solved by the following aspects, and have thus completed the present invention. [1]: A thermosetting composition comprising a polyimide resin (A) and a crosslinking agent (B) having two or more functional groups, The polyimide resin (A) is represented by the general formula (1): [ka] (X 1 is independently a tetravalent tetracarboxylic acid residue for each repeating unit, and X 2 are each independently a divalent organic group for each repeating unit, and 1 and imide bonds bond together to form two imide rings.) and has a phenolic hydroxyl group, X 2 At least a portion of the residues X are derived from dimer diamine and / or dimer diisocyanate. 2 d, Polyimide resin (A) has a storage modulus G' of 1.0 x 10 7 The temperature at which Pa is reached is between 30 and 90°C. the crosslinking agent (B) comprises one or more compounds selected from the group consisting of an epoxy group-containing compound (b1), a cyanate ester compound (b2), an isocyanate group-containing compound (b3), a metal chelate compound (b4), a carbodiimide group-containing compound (b5), and a maleimide group-containing compound (b6); A thermosetting composition, wherein the total content of the epoxy group-containing compound (b1), the cyanate ester compound (b2), the isocyanate group-containing compound (b3), the metal chelate compound (b4), the carbodiimide group-containing compound (b5) and the maleimide group-containing compound (b6) is 0.5 to 10 parts by mass per 100 parts by mass of the polyimide resin (A). [2]: The thermosetting composition according to [1], characterized in that the glass transition temperature after thermal curing under conditions of 180°C for 60 minutes is 0 to 70°C. [3]: The thermosetting composition according to [1] or [2], wherein the phenolic hydroxyl group satisfies at least one of the following (i) to (iv): (i) It has a phenolic hydroxyl group at the molecular chain terminal, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the meta or ortho position of the aromatic ring having the phenolic hydroxyl group. (ii) It has a phenolic hydroxyl group at the molecular chain terminal, an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the aliphatic group. (iii) the above X 2 A part of the diamine residue X having a phenolic hydroxyl group 2 f, and a nitrogen atom forming an imide ring derived from a diamine is bonded to the aromatic ring having the phenolic hydroxyl group. (iv) The above X 2 A part of the diamine residue X having a phenolic hydroxyl group 2 f, which has an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom forming an imide ring derived from a diamine is bonded to the aliphatic group. [4]: The X in the polyimide resin (A) 1 At least a portion of X has an aliphatic group 1 a, and the X 1 With respect to 100 mol%, the X 1 The thermosetting composition according to any one of [1] to [3], characterized in that it contains 60 to 100 mol % of a. [5]: The thermosetting composition according to any one of [1] to [4], characterized in that it contains 0.1 to 10 mass % of the ultraviolet absorber (C) relative to 100 mass % of the nonvolatile content. [6]: The thermosetting composition according to any one of [1] to [5], characterized in that it contains 3 to 60 mass % of the filler (D) relative to 100 mass % of the nonvolatile content. [7]: An adhesive sheet comprising the thermosetting composition according to any one of [1] to [6]. [8]: A printed wiring board formed using the adhesive sheet according to [7]. [9]: An electronic device having the printed wiring board according to [8]. [Effects of the Invention]
[0010] The present invention has the excellent effect of providing a thermosetting composition and adhesive sheet that have excellent lamination properties to LCP substrates and that, upon curing, give a cured product that has excellent plating solution resistance (alkali resistance and acid resistance) and excellent insulation reliability after a heat cycle test, as well as a printed wiring board and electronic device formed using this adhesive sheet. [Brief explanation of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic top view for explaining an evaluation board according to the present embodiment. [Figure 2] FIG. 2 is a schematic top view for explaining an evaluation board according to the present embodiment. [Figure 3] FIG. 2 is a schematic top view for explaining an evaluation board according to the present embodiment. [Figure 4] 4 is a cross-sectional view taken along line IV-IV of FIG. 3. [Figure 5] 1A to 1C are schematic explanatory views of a laser processing evaluation method according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0012] The present invention will be described in detail below. Needless to say, other embodiments are also included within the scope of the present invention as long as they are consistent with the spirit of the present invention. Furthermore, in this specification, a numerical range specified using "to" includes the numerical values before and after "to" as the range of the lower and upper limits. Furthermore, in this specification, "film" and "sheet" are synonymous and are not distinguished by thickness. Furthermore, unless otherwise noted, the various components appearing in this specification may be used independently, either singly or in combination of two or more types. The numerical values described in this specification refer to values obtained by the methods described in the Examples below.
[0013] 1.Thermosetting composition The thermosetting composition according to this embodiment (hereinafter also referred to as the present composition) contains a polyimide resin (A) and a crosslinking agent (B) having two or more functional groups. The polyimide resin (A) has a repeating unit having a structure represented by the following general formula (1) and also has a phenolic hydroxyl group. [ka] X in formula (1) 1 is independently a tetravalent tetracarboxylic acid residue for each repeating unit, and X 2 X represents a divalent organic group independently for each repeating unit. 1 and imide bonds are bonded to each other to form two imide rings. 2 At least a portion of the residues X are derived from dimer diamine and / or dimer diisocyanate. 2 d (hereinafter also referred to as a dimer structure).
[0014] In this specification, the term "tetracarboxylic acid residue" refers to a group derived from a tetracarboxylic acid and tetracarboxylic acid derivatives such as tetracarboxylic acid dianhydrides and tetracarboxylic acid diesters (hereinafter referred to as "tetracarboxylic acids"). In the above formula (1), the term "organic group" refers to a group derived from an organic compound having a functional group that reacts with tetracarboxylic acids. An imide bond is obtained by the reaction of tetracarboxylic acids with the organic compound. Suitable examples of the organic compound include diamines and diisocyanates.
[0015] An "imido bond" is defined as a bond consisting of one nitrogen atom and two carbonyl bonds (C=O), and is defined as the bond between the imido bond and X in formula (1). 1 are bonded to each other to form an imide ring. An "imide ring" is a ring having an imide bond, and the number of elements forming one ring is 4 or more and 7 or less, preferably 5 or 6. The imide ring may be condensed with another ring. Furthermore, an "acid anhydride group" refers to a group represented by -C(=O)-OC(=O)-, and an "acid anhydride ring" refers to a ring formed by bonding an acid anhydride group and a carbon element.
[0016] The crosslinking agent (B) includes one or more compounds selected from the group consisting of an epoxy group-containing compound (b1), a cyanate ester compound (b2), an isocyanate group-containing compound (b3), a metal chelate compound (b4), a carbodiimide group-containing compound (b5), and a maleimide group-containing compound (b6) (hereinafter also referred to as (b1) to (b6)). The total content of (b1) to (b6) is 0.5 to 10 parts by mass per 100 parts by mass of the polyimide resin (A). Here, the term "thermosetting composition" refers to a composition that contains a thermosetting resin and hardens by forming a three-dimensional crosslinked resin structure through a heat curing treatment. In this specification, the term "cured product" refers to a composition that has been cured to the extent that further heating does not substantially promote the curing reaction. When the thermosetting composition is molded into a desired shape such as a sheet, a portion of the composition may undergo a curing reaction, but the state in which the composition can be cured by further heating is not included in the term "cured product." The thermosetting composition may also be in a B-stage state in which some of the components are semi-cured.
[0017] Conventionally, LCP substrates are prone to temporary adhesion defects, and a composition that allows lamination at low temperatures and in a short time has been desired. This composition has the above-mentioned structure, and therefore has excellent lamination properties to LCP substrates. This is because the storage modulus G' is 1.0 x 10 7 This is thought to be due to the synergistic effect of using a highly flexible resin whose Pa temperature is between 30 and 90°C, the affinity to LCP substrates due to the phenolic hydroxyl groups, and the high wettability due to the dimer structure. A thermosetting sheet formed from this composition can provide a thermosetting composition that has excellent lamination properties for LCP substrates, even when heated at a low temperature of, for example, 90 to 100°C for a heating time of about 60 to 120 seconds.
[0018] Furthermore, since the composition has the above-mentioned structure, a cured product having excellent alkali resistance and acid resistance (hereinafter collectively referred to as plating solution resistance) can be obtained. The alkali resistance and acid resistance in this specification refer to the resistance evaluated in the examples described later. In particular, the composition has a dimer structure and a storage modulus G' of 1.0 x 10 7 The temperature at which the viscosity of the cured product reaches Pa falls within the above-mentioned specific range, and the polyimide resin (A) having phenolic hydroxyl groups introduced therein can significantly improve the plating solution resistance of the cured product. This is thought to be due to the fact that the inclusion of any of (b1) to (b6) as the crosslinking agent (B) allows the formation of a crosslinked structure between the phenolic hydroxyl groups of the polyimide resin (A) and the crosslinking agent (B), resulting in the interaction between the aromatic ring of the phenolic hydroxyl group and the imide ring of the polyimide resin (A) in the vicinity of the crosslink. Another effect is thought to be due to the construction of a strong crosslinked structure by crosslinking the phenolic hydroxyl groups of the polyimide resin (A) with the crosslinking agent (B). Although the reactive functional groups in the polyimide resin (A) are crosslinked with the crosslinking agent (B) by thermal curing, some of the reactive functional groups may remain without crosslinking. When the remaining functional groups are phenolic hydroxyl groups, the acid resistance and alkali resistance can be improved compared to when, for example, acid anhydride groups, carboxy groups, and / or amino groups remain. Furthermore, even when phenolic hydroxyl groups are used in combination with acid anhydride groups, carboxy groups, and / or amino groups, the amount of remaining carboxy groups can be further reduced, and therefore, improved acid resistance and alkali resistance can be expected.
[0019] Furthermore, because this composition has the above-mentioned structure, a cured product with excellent insulation reliability can be obtained even after heat cycle testing. By using a polyimide resin (A) that satisfies the storage modulus G' requirement and further has a dimer structure containing hydrocarbon chains or ring structures and little interaction between molecular chains, the packing around the highly planar imide rings can be moderately inhibited, achieving both uniform dispersion of the imide rings and flexibility. By blending a relatively small amount of the specific crosslinking agent (B) described above with such a polyimide resin (A), the cured product of this composition can be made to relieve stress caused by sudden temperature changes during heat cycles, thereby suppressing cracking and other problems. As a result, it is believed that excellent insulation reliability can be achieved even after heat cycle testing.
[0020] The present composition is suitable for various sheets and films, including thermosetting adhesive sheets and thermosetting cover sheets. These are used by laminating a layer formed from the present composition with another substrate or layer. Any known lamination method can be used without limitation. Examples include coating and lamination. The lamination method is advantageous in terms of simplicity. Below, the components of the present composition and the production method are described.
[0021] 1-1. Polyimide resin (A) As described above, the polyimide resin (A) has a repeating unit of the structure represented by the general formula (1) and also has a phenolic hydroxyl group. The position of the phenolic hydroxyl group in the polyimide resin (A) is not particularly limited. The polyimide resin (A) has a storage modulus G' of 1.0 x 10 7 The temperature at which the storage modulus G' reaches 100 Pa is between 30 and 90°C. Resins whose storage modulus G' satisfies the above conditions can soften at low temperatures and improve fluidity, thereby enhancing wettability to substrates, but have had the problem of being more prone to deterioration in plating solution resistance than conventional resins. As a result of extensive investigations, the present inventors have found that the present composition, which uses a polyimide resin (A) having a storage modulus within the above conditions and which has a phenolic hydroxyl group, can solve the above-mentioned problem of plating solution resistance. The polyimide resin (A) can be used alone or in combination of two or more types.
[0022] 1-1-a. X in general formula (1) 1 X in general formula (1) 1 As described above, X is a tetravalent tetracarboxylic acid residue, each of which may have an independent structure for each repeating unit. 1 The tetracarboxylic acids used in the polymerization to obtain X are not particularly limited. As the tetracarboxylic acids, aromatic tetracarboxylic acids containing an aromatic group, aliphatic tetracarboxylic acids containing an aliphatic group, and tetracarboxylic acids containing an aromatic group and an aliphatic group are preferably used. 1 The tetracarboxylic acids may contain heteroatoms such as nitrogen, oxygen, sulfur, selenium, fluorine, chlorine, and bromine. The tetracarboxylic acids may be used alone or in combination of two or more. The above-mentioned examples of monomers may also have a substituent, as appropriate. Examples of the substituent include an alkyl group, a halogen atom, a nitro group, and a cyano group.
[0023] Examples of aromatic tetracarboxylic acids include pyromellitic dianhydride, 1,2,3,4-benzenetetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, and diphthalic dianhydride represented by the following general formula (2): [ka] X in the formula 5 represents a divalent organic group which may have a substituent (for example, a hydrocarbon group having 1 to 10 carbon atoms), -O-, -CO-, -SO2-, -S-, -SO2-, -CONH-, -COO-, or a linking group such as -OCO-, -C(CF3)2-, -COO-Z-OCO-, or -O-Ph-C(CH3)2-Ph-O-. The Z may be, for example, -C6H4-, -(CH2) n Examples of the substituent include -, -CH2-CH(-OC(=O)-CH3)-CH2-. These may contain a substituent. Examples of the substituent include an alkyl group, a halogen, and a carbonyl group. The same applies to the tetracarboxylic acid described below. Specific examples include 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 4,4'-(hexafluoroisopropylidene)diphthalic anhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, p-phenylenebis(trimellitic acid monoester acid anhydride), and ethylene glycol bisanhydrotrimellitate.
[0024] From the viewpoint of effectively improving lamination onto an LCP substrate at low temperatures and further improving insulation reliability after heat cycles, X in general formula (1) 1 At least a portion of X has an aliphatic group 1 It is preferable that X is a. 1a has only to have an aliphatic group, and may also contain an aromatic group.
[0025] Tetracarboxylic acids having an aliphatic group include chain hydrocarbon structures and / or alicyclic hydrocarbon structures which may contain an aromatic group. The "chain hydrocarbon structure" refers to a linear hydrocarbon structure and / or a branched hydrocarbon structure which may contain an unsaturated bond. The "alicyclic hydrocarbon structure" refers to an alicyclic hydrocarbon which may contain an unsaturated bond, and may be monocyclic or polycyclic. These may contain a substituent.
[0026] Specific examples of tetracarboxylic acids having an aliphatic group include tetracarboxylic dianhydrides having a chain hydrocarbon structure, such as 1,2,3,4-butanetetracarboxylic acid, 1,2,3,4-pentanetetracarboxylic acid, 1,2,4,5-pentanetetracarboxylic acid, 1,2,3,4-hexanetetracarboxylic acid, and 1,2,5,6-hexanetetracarboxylic acid. Also, cyclobutane-1,2,3,4-tetracarboxylic acid, cyclopentane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,3,4-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, 1-carboxymethyl-2,3,5-cyclopentanetricarboxylic acid, 3-carboxymethyl-1,2,4-cyclopentanetricarboxylic acid, rel-dicyclohexyl-3,3',4,4'-tetracarboxylic acid, tricyclo[4.2.2.02,5]deca 1,9-ene-3,4,7,8-tetracarboxylic acid, 5-carboxymethylbicyclo[2.2.1]heptane-2,3,6-tricarboxylic acid, bicyclo[2.2.1]heptane-2,3,5,6-tetracarboxylic acid, bicyclo[2.2.2]octane-7-ene-2,3,6,7-tetracarboxylic acid, bicyclo[3.3.0]octane-2,4,6,7-tetracarboxylic acid, 7,8-diphenylbicyclo[2.2.2]octane-7-ene-2,3,5,6-tetracarboxylic acid, 4,8-diphenylbicyclo[2.2.2]octane-7-ene-2,3,5,6-tetracarboxylic acid, Cyclo-, bicyclo-, and tricyclotetracarboxylic acids such as phenyl-1,5-diazabicyclooctane-2,3,6,7-tetracarboxylic acid, 9-oxatricyclo[4.2.1.02,5]nonane-3,4,7,8-tetracarboxylic acid, and 9,14-dioxopentacyclo[8.2.11,11.14,7.02,10.03,8]tetradecane-5,6,12,13-tetracarboxylic acid; spiro ring-containing tetracarboxylic acids such as 2,8-dioxaspiro[4.5]decane-1,3,7,9-tetracarboxylic acid; tetracarboxylic acid dianhydrides having an alicyclic hydrocarbon structure, such as 5-(2,5-dioxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic acid anhydride, 1,3,3a,4,5,9b-hexahydro-5(tetrahydro-2,5-dioxo-3-furanyl)naphtho[1,2-c]furan-1,3-dione, and 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid anhydride, can be exemplified.
[0027] From the viewpoint of more effectively improving lamination onto LCP substrates at low temperatures, X having an aliphatic group is preferred. 1It is preferred that a has a structure S that satisfies at least one of the following (I) and (II): (I) X constituting the imide ring in general formula (1) 1 is X 1 At least one of the carbon atoms in a is a carbon atom of X constituting the other imide ring. 1 At least one of the carbon atoms in a is directly bonded to the other. (II) X constituting each of the two imide rings in general formula (1) 1 is X 1 At least one of the carbon atoms in a independently satisfies either one of the following conditions: it is directly bonded to a chain hydrocarbon structure or an alicyclic hydrocarbon structure, or it is one of the constituent elements of the alicyclic hydrocarbon structure. Specific examples of compounds that satisfy the above condition (I) include chemical formulas (Ia) to (Id). Note that chemical formulas (Ib) to (Id) also satisfy the above condition (II). In the formulas, * indicates the bonding site with the imide group. [ka]
[0028] Specific examples that satisfy the above (II) include chemical formulas (II-a) to (II-v).
[0029] [ka]
[0030] X forms an imide ring 1 X having structure S, where the carbon in a is directly connected to a chain hydrocarbon structure 1 An example of a is a compound represented by the chemical formula (II-a). X forming an imide ring 1 X having the structure S, in which the carbon in the molecule is one of the constituent elements of an alicyclic hydrocarbon structure 1 An example of a is a compound represented by the chemical formula (II-b). 1 The carbon atom of a is directly bonded to the alicyclic hydrocarbon structure, and the carbon atom of X that forms the other imide ring 1X having structure S, in which the carbon in a is one of the constituent elements of an alicyclic hydrocarbon structure 1 An example of a is represented by chemical formula (II-c). Note that the two imide rings may each independently satisfy at least one of the above (I) and (II), and may contain an aromatic ring as shown in chemical formula (II-d).
[0031] X having an aliphatic group 1 The proportion of a is the ratio of X that constitutes the polyimide resin (A). 1 The content of X having an aliphatic group is preferably 60 to 100 mol %, more preferably 75 to 100 mol %, and even more preferably 85 to 100 mol % relative to 100 mol %. 1 By using 60 to 100 mol % of a, the lamination property to LCP becomes more excellent. 1 The proportion of a is determined by the ratio of X to X among the raw material monomers used in synthesizing polyimide resin (A). 1 The ratio of X having an aliphatic group to 100 mol % of all monomers that become residues 1 It can be calculated from the content (mol %) of the monomer that forms the residue of a. Usually, the ratio of the monomers used during synthesis is the same as the constituent ratio in the resin.
[0032] 1-1-b. X in general formula (1) 2 X in general formula (1) 2 As described above, X is a divalent organic group which may have an independent structure for each repeating unit. 2 As mentioned above, suitable examples of organic compounds used in the polymerization to obtain X include diamines and diisocyanates. 2 At least a portion of the residues X are derived from dimer diamine and / or dimer diisocyanate. 2 d.
[0033] Dimer diamines can be obtained, for example, by converting the carboxyl groups of dimer acids to amino groups. Dimer diisocyanates can be obtained, for example, by converting the carboxyl groups of dimer acids to isocyanate groups. Here, dimer acids refer to the dimers of unsaturated aliphatic carboxylic acids or their hydrogenated products. For example, dimer acids can be obtained by dimerizing natural fatty acids such as soybean oil fatty acids, tall oil fatty acids, and rapeseed oil fatty acids, as well as unsaturated fatty acids purified from these, such as linolenic acid, linoleic acid, oleic acid, and erucic acid. The unsaturated bonds may be hydrogenated as needed to reduce the degree of unsaturation. Dimer diamines and dimer diisocyanates with reduced degrees of unsaturation are advantageous in terms of oxidation resistance (especially coloration at high temperatures) and suppression of gelation during synthesis.
[0034] The dimer acid is preferably a compound having 20 to 60 carbon atoms, more preferably a compound having 24 to 56 carbon atoms, even more preferably a compound having 28 to 48 carbon atoms, and particularly preferably a compound having 36 to 44 carbon atoms. Dicarboxylic acid compounds having a branched structure obtained by subjecting a fatty acid to a Diels-Alder reaction are preferred. The branched structure is preferably an aliphatic chain or a cyclic structure, more preferably a cyclic structure. The cyclic structure is preferably one or more aromatic rings or an alicyclic structure, more preferably an alicyclic structure. When there are two cyclic structures, the two rings may be independent or continuous. One or more dimer diamine and dimer diisocyanate compounds can be used. The alicyclic structure may have one or more double bonds within the ring, or may have no double bond. Methods for converting the carboxy group of a dimer acid to an amino group include, for example, amidating the carboxylic acid, converting it to an amine by Hofmann rearrangement, and then distilling and purifying the resulting mixture. The carboxy group of the dimer acid can be converted into a diisocyanate group, for example, by converting a carboxylic acid into an isocyanate group through Curtius rearrangement.
[0035] The amino group in the dimer diamine or the isocyanate group in the dimer diisocyanate may be directly bonded to the ring structure, but from the viewpoint of improving solubility and flexibility, it is preferable that the amino group be bonded to the ring structure via an aliphatic chain. The number of carbon atoms between the amino group or isocyanate group and the ring structure is preferably 2 to 25. A suitable example of the aliphatic chain is a linear hydrocarbon group such as an alkylene group. A suitable example is a compound in which the two amino groups or isocyanate groups are each bonded to a ring structure via an alkylene group.
[0036] Specific examples of dimer acids (polybasic acids) for obtaining dimer diamine or dimer diisocyanate include the following chemical formulas (d1) to (d4). These are just examples, and the dimer acid is not limited to the following structures.
[0037] [ka] [ka] [ka] [ka]
[0038] The dimer diamine and dimer diisocyanate are preferably compounds having 20 to 60 carbon atoms, more preferably compounds having 24 to 56 carbon atoms, even more preferably compounds having 28 to 48 carbon atoms, and still more preferably compounds having 36 to 44 carbon atoms. Such carbon numbers are preferred from the viewpoint of ease of availability.
[0039] Commercially available dimer diamine products include, for example, "Priamine 1071," "Priamine 1073," "Priamine 1074," and "Priamine 1075" manufactured by Croda Japan, and "Versamin 551" manufactured by BASF Japan.
[0040] Dimeric structure of residue X 2 The proportion of monomers that yield d is X 2 The content is preferably 80 to 100% by mass per 100% by mass of the monomer from which the residue is obtained. By making it 80% by mass or more, the lamination property to the LCP substrate at low temperatures becomes better. The above range is more preferably 83 to 100% by mass, and even more preferably 85 to 100% by mass. X having a dimer structure 2 The proportion of d is determined by the ratio of X to X among the raw material monomers used in synthesizing polyimide resin (A). 2 The proportion of X having a dimer structure in 100% by mass of all monomers that become residues 2 d can be calculated from the content (mass%) of the monomer that becomes the residue. Usually, the ratio of the monomers used during synthesis is the same as the constituent ratio in the resin.
[0041] X in general formula (1) 2 Examples of the diamines include those having a phenolic hydroxyl group, which will be described later. 2 Diamines other than the monomers forming d and diamines having a phenolic hydroxyl group can be used as appropriate. Examples include diamine compounds having an aliphatic group (a chain hydrocarbon structure and / or an alicyclic hydrocarbon structure that may contain an unsaturated bond), which may have a substituent, an aromatic ring, and any combination thereof.
[0042] Other diamines include, for example, 1,4-diaminobenzene, 1,3-diaminobenzene, 1,2-diaminobenzene, 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, 2,3-diaminonaphthalene, 2,6-diaminotoluene, 2,4-diaminotoluene, 3,4-diaminotoluene, 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenyl ether, 4,4'-diamino-1,2-diphenylethane, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'-diamino Examples of the diamine include aromatic diamines such as diphenyl sulfone, 3,3'-diaminobenzophenone, and 3,3'-diaminodiphenyl sulfone; aliphatic diamines such as ethylene diamine, 1,3-propane diamine, 1,4-butane diamine, 1,6-hexane diamine, 1,7-heptane diamine, 1,9-nonane diamine, 1,12-dodecamethylene diamine, and meta-xylene diamine; and alicyclic diamines such as isophorone diamine, norbornane diamine, 1,2-cyclohexane diamine, 1,3-cyclohexane diamine, 1,4-cyclohexane diamine, 4,4'-diaminodicyclohexylmethane, and piperazine.
[0043] 1-1-c. Phenolic hydroxyl group As described above, the polyimide resin (A) has a phenolic hydroxyl group. The phenolic hydroxyl group refers to a hydroxyl group directly bonded to an aromatic ring. Suitable examples of the aromatic ring include a benzene ring, a naphthalene ring, and a pyridine ring. The phenolic hydroxyl group can be introduced into the molecular chain terminal of the polyimide resin (A), or into a side chain or side group of the main chain skeleton. The phenolic hydroxyl group can be introduced into either the molecular chain terminal, side group, or side chain, or any combination thereof. The molecular chain terminal refers to a repeating structural unit at the terminal of the molecular chain of the polyimide resin (A), or a non-repeating structure linked to that terminal.
[0044] The phenolic hydroxyl value of the polyimide resin (A) is preferably 1 to 30 mgKOH / g. By adjusting the phenolic hydroxyl value within this range, the crosslink density can be optimized, and plating solution resistance (alkali resistance and acid resistance) can be more effectively improved. Furthermore, by adjusting the phenolic hydroxyl value within this range, the crosslink density can be optimized, resulting in a stress relaxation effect and more effectively improving insulation reliability after a heat cycle test. The phenolic hydroxyl value is more preferably 3 to 20 mgKOH / g, and even more preferably 5 to 15 mgKOH / g. The phenolic hydroxyl value can be adjusted by the amount of monomer containing a phenolic hydroxyl group, the introduction rate of phenolic hydroxyl groups into molecular chain terminals, and / or the introduction rate of phenolic hydroxyl groups into side chains.
[0045] Suitable examples of polyimide resin (A) include polyimide resin (A) in which all or some of the functional groups at the molecular chain terminals are phenolic hydroxyl groups and no phenolic hydroxyl groups are present in the side groups / side chains; polyimide resin (A) in which all or some of the functional groups at the molecular chain terminals are phenolic hydroxyl groups and also have phenolic hydroxyl groups in the side groups / side chains; polyimide resin (A) in which the molecular chain terminals are end-capped and have phenolic hydroxyl groups in the side groups or side chains; and polyimide resin (A) in which the molecular chain terminals are other functional groups such as acid anhydride groups and have phenolic hydroxyl groups in the side groups or side chains. Among these, from the viewpoint of plating solution resistance, polyimide resin (A) in which substantially all of the functional groups at the molecular chain terminals are phenolic hydroxyl groups and polyimide resin (A) in which the molecular chain terminals consist of phenolic hydroxyl groups and molecular chain terminals without functional groups are particularly preferred. The polyimide resin (A) may have other functional groups, such as acid anhydride groups, amino groups, and carboxy groups, at molecular chain terminals, side groups, and / or side chains, without departing from the spirit of the present invention. When the polyimide resin (A) contains acid anhydride groups, the acid anhydride group value is preferably 15 mg KOH / g or less, more preferably 10 mg KOH / g or less, and even more preferably 5 mg KOH / g or less, from the viewpoint of plating solution resistance. When the polyimide resin (A) contains amino groups, the amine value is preferably 15 mg KOH / g or less, more preferably 10 mg KOH / g or less, and even more preferably 5 mg KOH / g or less, from the viewpoint of plating solution resistance.
[0046] 1-1-c1.Molecular chain end To introduce phenolic hydroxyl groups into the molecular chain terminals of polyimide resin (A), an example is a method in which an acid anhydride-terminated polyimide resin is synthesized and then reacted with an amine compound having a phenolic hydroxyl group represented by general formula (3). Phenolic hydroxyl groups may also be introduced by a similar method, except that the acid anhydride-terminated polyimide resin is replaced with a carboxylic acid-terminated polyimide resin. [ka] In general formula (3), Ar is an aromatic group which may have a substituent. Examples of the substituent include an alkyl group or a fluoroalkyl group having 1 to 10 carbon atoms, and a halogen atom. In addition to compounds in which the amino group in general formula (3) is directly bonded to the aromatic group, compounds in which the amino group is bonded to the aromatic group via an aliphatic group are also suitable. The same applies to Ar and the substituents in general formulas (4) and (5) described below.
[0047] Another example is a method in which an amino-terminated polyimide resin is synthesized and then further reacted with an acid anhydride compound having a phenolic hydroxyl group represented by general formula (4) or a carboxylic acid compound having a phenolic hydroxyl group represented by general formula (5) to introduce a phenolic hydroxyl group at the terminal.
[0048] [ka] [ka]
[0049] Specific examples of general formula (3) include 3-aminophenol, 4-aminophenol, 4-amino-o-cresol, 5-amino-o-cresol, 4-amino-2,3-xylenol, 4-amino-2,5-xylenol, 4-amino-2,6-xylenol, 4-amino-1-naphthol, 5-amino-2-naphthol, 6-amino-1-naphthol, and 4-amino-2,6-diphenylphenol. Specific examples of general formula (4) include 3-hydroxyphthalic anhydride and 4-hydroxyphthalic anhydride. Specific examples of general formula (5) include salicylic acid and hydroxybenzoic acid. While examples of general formulas (3) and (4) have been given with one hydroxyl group, compounds in which two or more hydroxyl groups are bonded to Ar may also be used.
[0050] From the viewpoint of more effectively improving the insulation reliability of the cured product after a heat cycle test, a polyimide resin (A) having a phenolic hydroxyl group that satisfies at least one of the following (i) and (ii) is preferred. (i) It has a phenolic hydroxyl group at the molecular chain terminal, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the meta or ortho position of the aromatic ring having the phenolic hydroxyl group. (ii) It has a phenolic hydroxyl group at the molecular chain terminal, an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the aliphatic group. By having a phenolic hydroxyl group that satisfies at least one of the above (i) and (ii), the insulating reliability of the cured product of this composition after a heat cycle test can be more effectively improved. Through extensive research, the inventors have found that the structure surrounding the phenolic hydroxyl group at the molecular chain terminal is the structure surrounding the crosslinking point, and therefore has a significant impact on stress relaxation. It is believed that the structure (i), in which the hydroxyl group and the amino group are located in the ortho or meta position, reduces the interaction between the imide ring and other imide rings, thereby improving stress relaxation. Furthermore, it is believed that the structure (ii), in which the amino group is bonded via an aliphatic group rather than directly to an aromatic ring, reduces the interaction between the imide ring and other imide rings, thereby improving stress relaxation.
[0051] Examples of monoamine compounds having a phenolic hydroxyl group that can be used to end-capping acid anhydride-terminated polyimide resins or carboxyl-terminated polyimide resins to obtain molecular chain ends that satisfy the above (i) and (ii) include m-aminophenol, o-aminophenol, 2-amino-5-ethylphenol, 2-(1-aminoethyl)phenol, 3-(2-aminoethyl)phenol, 4-(2-aminoethyl)phenol, 2-(2-aminoethyl)phenol, 2-(2-aminomethyl)phenol, 3-(2-aminomethyl)phenol, 2-(2-aminomethyl)phenol, 3-(2-aminomethyl)phenol, and 4-(2-aminopropyl)phenol.
[0052] The functional groups at the molecular chain terminals of the polyimide resin (A) can be substantially all phenolic hydroxyl groups. Furthermore, in addition to the phenolic hydroxyl group terminals, the polyimide resin (A) may also contain molecular chain terminals without functional groups. Furthermore, in addition to the phenolic hydroxyl group terminals, the polyimide resin (A) may also contain molecular chain terminals with other functional groups (such as acid anhydride groups).
[0053] A polyimide resin (A) having molecular chain terminals without functional groups and phenolic hydroxyl groups can be obtained, for example, by mixing an amine compound of general formula (3) and a monoamine compound without phenolic hydroxyl groups in a specific ratio with an acid anhydride-terminated polyimide and then performing an end-capping reaction. Alternatively, the polyimide can be obtained by mixing a compound of general formula (4) and / or (5) with an acid anhydride compound and / or a carboxylic acid compound without phenolic hydroxyl groups in a specific ratio with an amine-terminated polyimide and then performing an end-capping reaction. These methods allow the amount of phenolic hydroxyl groups at the molecular chain terminals of the polyimide resin (A) to be easily adjusted.
[0054] Examples of monoamine compounds having no phenolic hydroxyl group include aliphatic amines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, and dibutylamine; alicyclic amines such as cyclohexylamine and dicyclohexylamine; aromatic amines such as aniline, toluidine, diphenylamine, and naphthylamine, and any mixtures thereof.
[0055] Examples of acid anhydrides that do not have a phenolic hydroxyl group include phthalic anhydride, 2,2'-biphenyldicarboxylic anhydride, 1,2-naphthalenedicarboxylic anhydride, 2,3-naphthalenedicarboxylic anhydride, 1,8-naphthalenedicarboxylic anhydride, 1,2-anthracenedicarboxylic anhydride, 2,3-anthracenedicarboxylic anhydride, L9-anthracenedicarboxylic anhydride, etc. Examples of carboxylic acids that do not have a phenolic hydroxyl group include carboxylic acids having a structure in which the phenolic hydroxyl group has been removed from the above-mentioned carboxylic acids that have a phenolic hydroxyl group.
[0056] A polyimide resin (A) having a phenolic hydroxyl group at its terminal and another functional group at its terminal can be obtained, for example, by mixing an amine compound of general formula (3) with a monoamine compound having another functional group in a specific ratio with an acid anhydride-terminated polyimide and then performing an end-capping reaction. Similarly, an amine-terminated polyimide can be obtained by mixing a compound of general formula (4) and / or (5) with an acid anhydride compound and / or a carboxylic acid compound having another functional group in a specific ratio and then performing an end-capping reaction. This method allows the amount of phenolic hydroxyl groups and other functional groups at the molecular chain terminals of the polyimide resin (A) to be adjusted. The other functional groups are not particularly limited. Examples include nitro and cyano groups.
[0057] When the other functional group is an acid anhydride group, an acid anhydride-terminated polyimide may be synthesized, and then reacted with an amine compound having a phenolic hydroxyl group at a portion of the terminal to convert a portion of the acid anhydride terminal to a phenolic hydroxyl group. Similarly, when the other functional group is an amino group, an amino-terminated polyimide may be synthesized, and then reacted with a compound having one acid anhydride group having a phenolic hydroxyl group at a portion of the terminal.
[0058] In the above, an example was given in which a polyimide resin is synthesized and then reacted with a compound to be introduced into the molecular chain terminal, but polyimide resin (A) may also be synthesized by mixing the compound to be introduced into the molecular chain terminal with the monomer for synthesizing the polyimide resin and polymerizing them. This method can simplify the synthesis process.
[0059] From the viewpoint of improving the insulation reliability after a heat cycle test and plating solution resistance (alkali resistance and acid resistance), the molecular chain terminals having phenolic hydroxyl groups are preferably 50 to 100 mol %, and more preferably 70 to 100 mol %, relative to 100 mol % of the functional groups at the molecular chain terminals of the polyimide resin (A). By introducing phenolic hydroxyl groups into the molecular chain terminals of the polyimide resin (A), the crosslink density with the crosslinking agent (B) can be optimized, effectively deriving a stress relaxation effect. As a result, it is believed that good insulation reliability can be maintained after a heat cycle test.
[0060] 1-1-c2. Side chains and side groups To introduce phenolic hydroxyl groups into the side chains and / or side groups of the polyimide resin (A), a method using an organic compound such as a diamine or diisocyanate having a phenolic hydroxyl group and / or a tetracarboxylic acid having a phenolic hydroxyl group is preferred. Alternatively, after synthesizing the polyimide resin, a compound having a phenolic hydroxyl group may be introduced into the side chain. When introducing phenolic hydroxyl groups into the side chain, the phenolic hydroxyl value can be appropriately designed, but a value of 1 to 5 mgKOH / g is preferred from the viewpoint of more effectively exhibiting plating solution resistance and insulation reliability after heat cycles.
[0061] Suitable examples of diamines having a phenolic hydroxyl group include aromatic diamines such as bis(3-amino-4-hydroxyphenyl)hexafluoropropane, bis(3-amino-4-hydroxyphenyl)sulfone, bis(3-amino-4-hydroxyphenyl)propane, bis(3-amino-4-hydroxyphenyl)methylene, bis(3-amino-4-hydroxyphenyl)ether, bis(3-amino-4-hydroxy)biphenyl, 2,2'-ditrifluoromethyl-5,5'-dihydroxyl-4,4'-diaminobiphenyl, bis(3-amino-4-hydroxyphenyl)fluorene, and 2,2'-bis(trifluoromethyl)-5,5'-dihydroxybenzidine. Substituents may also be introduced at any position in these compounds.
[0062] Alternatively, a diamine represented by the following general formula (6) may be used. [ka]
[0063] R in the formula 1 represents a direct bond or a group containing carbon, hydrogen, oxygen, nitrogen, sulfur, or halogen. Examples of the group include a divalent hydrocarbon group having 1 to 30 carbon atoms, a divalent hydrocarbon group having 1 to 30 carbon atoms in which some or all of the hydrogen atoms have been substituted with halogen atoms, -(C=O)-, -SO2-, -O-, -S-, -NH-(C=O)-, -(C=O)-O-, a group represented by the following general formula (7), and a group represented by the following general formula (8). In the formula, r and s each independently represent an integer of 1 to 20, and R 2 represents a hydrogen atom or a methyl group.
[0064] [ka]
[0065] [ka]
[0066] Examples of diamines represented by general formula (6) include 2,2-bis(3-amino-4-hydroxyphenyl)propane, 9,9-bis(3-amino-4-hydroxyphenyl)fluorene, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane, and 4,4'-diamino-3,3'-dihydroxybisphenyl.
[0067] Suitable examples of tetracarboxylic acids having a phenolic hydroxyl group include aromatic tetracarboxylic acids described below, which have a hydroxyl group as a substituent on the aromatic group.
[0068] Among these, from the viewpoint of more effectively improving plating solution resistance, diamines containing a phenolic hydroxyl group that satisfy at least one of the following (iii) and (iv) are preferred. (iii) X in general formula (1) 2 A part of the diamine residue X containing a phenolic hydroxyl group 2 f, and a nitrogen atom derived from the diamine forming the imide ring is bonded to the aromatic ring having the phenolic hydroxyl group. (iv) X in general formula (1) 2 A part of the diamine residue X having a phenolic hydroxyl group 2 f, which has an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom derived from the diamine that forms the imide ring is bonded to the aliphatic group. By having a phenolic hydroxyl group that satisfies at least one of the above (iii) and (iv), the plating solution resistance and insulating reliability after heat cycles of the cured product of the composition can be more effectively improved. By using a side group of the polyimide resin (A) as the crosslinking point with the crosslinking agent (B), a crosslinked structure can be effectively formed.
[0069] Suitable examples of diamines that satisfy the above (iii) or (iv) include the following general formulas (9) and (10): In formula (9), n is an integer of 1-10. [ka]
[0070] [ka]
[0071] 1-1-d. Other monomers The polyimide resin (A) may contain X within the scope of the present invention. 1 residue, X 2The polyamine compound may contain residues derived from monomers other than the amino groups. For example, a polyamine compound having three or more amino groups may be used. Examples of polyamine compounds having three or more amino groups include 1,2,4-triaminobenzene and 3,4,4'-triaminodiphenyl ether.
[0072] 1-1-e. Manufacturing method of polyimide resin (A) The polyimide resin (A) can be produced by various known methods. Specific examples include a method in which a polyamic acid resin or a polyamic acid ester resin, which is a polyimide precursor, is cyclized by heating to convert it to an imide group. One example of a method for synthesizing a polyamic acid resin is a method in which a tetracarboxylic acid dianhydride is reacted with a diamine. More specifically, a polyamic acid resin, which is a polyimide precursor, can be produced by dissolving a monomer containing a tetracarboxylic acid dianhydride and a diamine in a solvent and stirring the resulting mixture at a temperature of, for example, 60 to 120°C for 0.1 to 2 hours to polymerize it. The equivalent ratio (molar ratio) of the tetracarboxylic acid to the diamine or the like is, for example, 0.7 to 1.3, preferably 0.8 to 1.2. Another suitable method involves reacting a tetracarboxylic acid dianhydride with a diisocyanate to obtain a polyimide precursor, and then subsequently obtaining a polyimide resin.
[0073] When introducing a phenolic hydroxyl group into the molecular chain terminal, it can be introduced during the synthesis of a polyamic acid resin, or after the polyimide resin is obtained. The same applies to the case where it is introduced via a polyamic acid ester resin, which will be described later. When introducing a phenolic hydroxyl group into a side chain or side group, there are two methods: one is to use a compound having a phenolic hydroxyl group as a monomer for polymerizing polyimide resin (A), and the other is to introduce a phenolic hydroxyl group into a side chain or side group after synthesizing a polyimide resin precursor or polyimide resin.
[0074] Examples of methods for synthesizing polyamic acid ester resins include a method in which a diester is obtained from a tetracarboxylic dianhydride and an alcohol, and then the diester is reacted with a diamine in the presence of a condensing agent, and a method in which a diester is obtained from a tetracarboxylic dianhydride and an alcohol, and then the remaining dicarboxylic acid is converted into an acid chloride and reacted with a diamine.
[0075] Examples of organic solvents used in polymerization include N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Solvents can be used alone or in combination. Aromatic hydrocarbons such as xylene and toluene can also be used in combination.
[0076] The method for imidizing a polyimide precursor to obtain a polyimide resin is not particularly limited, but an example is a method in which the polyimide precursor is heated in a solvent at a temperature of 80 to 400°C for 0.5 to 50 hours. At this time, a catalyst and / or a dehydrating agent may be used as necessary. Examples of reaction catalysts include aliphatic tertiary amines such as triethylamine, aromatic tertiary amines such as dimethylaniline, and heterocyclic tertiary amines such as pyridine, picoline, and isoquinoline. Examples of dehydrating agents include aliphatic acid anhydrides such as acetic anhydride and aromatic acid anhydrides such as benzoic anhydride.
[0077] The imidization rate (the rate of imide ring formation) is not limited, but from the viewpoint of effectively exhibiting plating solution resistance (alkali resistance and acid resistance), it is preferably 80% or more, more preferably 90% or more, and even more preferably 95 to 100%. The imidization rate can be determined by NMR or IR analysis, etc.
[0078] 1-1-f. Properties of polyimide resin (A) The storage modulus G' of the polyimide resin (A) is 1.0 × 107 The temperature at which the storage modulus G' is 1.0 x 10 Pa is between 30 and 90°C. 7 It is more preferable that the storage modulus G' is 1.0 × 10 Pa at any temperature between 30 and 70°C. 7 It is more preferable that the polyimide resin (A) is contained in an amount of 50 to 98% by mass relative to 100% by mass of the solid content (non-volatile content) of the composition, although any amount can be used to improve lamination properties to an LCP substrate.
[0079] Storage modulus G' is 1.0 x 10 7 The polyimide resin (A) whose temperature at which Pa is reached is between 30 and 90°C can be adjusted by the type of monomer that constitutes the repeating structural unit and by the Mw. Specifically, the storage modulus G' tends to decrease when a flexible monomer such as a dimer structure is combined with a structure having an aliphatic (including alicyclic) skeleton. Conversely, the storage modulus G' tends to increase when a structure in which an imide structure is directly bonded to a highly planar aromatic skeleton is combined. Furthermore, the storage modulus G' tends to decrease by decreasing the Mw. The storage modulus G' at 90°C of a rigid polyimide resin, for example, a polyimide resin composed of pyromellitic acid and diaminobiphenyl, is approximately 1.0 x 10 9 The storage modulus G' at 90°C of a flexible polyimide resin, for example, a polyimide resin made of dimer diamine and 1,2,4,5-cyclohexanetetracarboxylic dianhydride, is approximately 1.0 × 10 5 is.
[0080] The weight-average molecular weight (Mw) of the polyimide resin (A) is not particularly limited, but is preferably 15,000 or more, and more preferably 20,000 or more, from the viewpoint of improving the insulation reliability of the cured product after a heat cycle test. The upper limit of Mw is not particularly limited, but is preferably 1,000,000, more preferably 100,000, and even more preferably 80,000, from the viewpoint of easy handling of the solution viscosity.
[0081] 1-2. Crosslinking agent (B) The crosslinking agent (B) is a compound that forms a crosslinked structure upon thermal curing and has two or more crosslinkable functional groups. The crosslinking agent (B) includes one or more compounds selected from the group consisting of epoxy group-containing compounds (b1), cyanate ester compounds (b2), isocyanate group-containing compounds (b3), metal chelate compounds (b4), carbodiimide group-containing compounds (b5), and maleimide group-containing compounds (b6). (b1) to (b6) may be used alone or in combination of two or more. It is sufficient to include the above (b1) to (b6), and other crosslinking agents may be used in combination within the scope of the present invention. By including any of (b1) to (b6) as the crosslinking agent (B), a crosslinked structure can be formed between the phenolic hydroxyl groups of the polyimide resin (A) and the crosslinking agent (B). The cured product may also include crosslinked structures between the crosslinking agents (B).
[0082] The total content of (b1) to (b6) of the crosslinking agent (B) is 0.5 to 10 parts by mass per 100 parts by mass of the polyimide resin (A). The total content of (b1) to (b6) of the crosslinking agent (B) is more preferably 1 to 8 parts by mass, even more preferably 2 to 6 parts by mass, and particularly preferably 3 to 5 parts by mass. The crosslinking agent (B) may be a low molecular weight compound or a high molecular weight compound. Note that the number of functional groups of the metal chelate compound (b4) described below is defined as the number of functional groups capable of forming coordinate bonds. For example, a metal chelate compound containing Al, Ti, and Zr is a trifunctional component. The average number of functional groups of the crosslinking agent (B) is calculated for each crosslinking agent (B) having the same skeleton.
[0083] The total content of (b1) to (b6) in 100% by mass of the crosslinking agent (B) is preferably 30 to 100% by mass, and more preferably 50 to 100% by mass.
[0084] From the viewpoint of achieving a balanced improvement in lamination properties with LCP substrates, plating solution resistance, insulation reliability after heat cycle testing, and laser processability after curing, the epoxy group-containing compound (b1) alone or a combination of the epoxy group-containing compound (b1) with one or more of (b2) to (b6) is preferred. Also preferred are combinations in which the crosslinking reaction between the crosslinking agents (B) proceeds.
[0085] 1-2-a. Epoxy group-containing compound (b1) The epoxy group-containing compound (b1) is not particularly limited as long as it has two or more epoxy groups in the molecule. Among the epoxy group-containing compounds (b1), compounds having an average number of epoxy groups of three or more functional groups are preferred. As the epoxy group-containing compound (b1), for example, an epoxy resin such as a glycidyl ether type epoxy resin, a glycidyl amine type epoxy resin, a glycidyl ester type epoxy resin, or a cyclic aliphatic (alicyclic) epoxy resin can be used.
[0086] Examples of the bifunctional epoxy group-containing compound (b1) include glycidyl ester epoxy resins such as diglycidyl phthalate, diglycidyl hexahydrophthalate, and diglycidyl tetrahydrophthalate; and cycloaliphatic (alicyclic) epoxy resins such as epoxycyclohexylmethyl-epoxycyclohexanecarboxylate and bis(epoxycyclohexyl)adipate. Other examples include bisphenol A epoxy resins, bisphenol F epoxy resins, bisphenol S epoxy resins, and bisphenol AD epoxy resins.
[0087] Examples of the epoxy group-containing compound (b1) having an average functionality of 3 or more include tris(glycidyloxyphenyl)methane and tetrakis(glycidyloxyphenyl)ethane, and examples of the glycidylamine type epoxy resin include tetraglycidyldiaminodiphenylmethane, triglycidyl paraaminophenol, triglycidyl metaaminophenol, or tetraglycidyl metaxylylenediamine, and sorbitol polyglycidyl ether.
[0088] Other examples of the epoxy group-containing compound (b1) include cresol novolac epoxy resins, phenol novolac epoxy resins, α-naphthol novolac epoxy resins, bisphenol A novolac epoxy resins, dicyclopentadiene epoxy resins, tetrabromobisphenol A epoxy resins, and brominated phenol novolac epoxy resins.
[0089] As the epoxy group-containing compound (b1), the above compounds can be used alone or in combination of two or more. From the viewpoint of high adhesiveness, it is preferable to use bisphenol A type epoxy resin, cresol novolac type epoxy resin, phenol novolac type epoxy resin, tris(glycidyloxyphenyl)methane, tetrakis(glycidyloxyphenyl)ethane, or tetraglycidylmeta-xylylenediamine.
[0090] 1-2-b. Cyanate ester compounds (b2) The cyanate ester compound (b2) refers to a compound having two or more cyanate groups. Specific examples include aromatic cyanate ester compounds such as 2,2-bis(4-cyanatephenyl)propane (bisphenol A-type cyanate resin), bis(3,5-dimethyl-4-cyanatephenyl)methane, 2,2-bis(4-cyanatephenyl)ethane, and derivatives thereof. These compounds may be used alone or in combination.
[0091] 1-2-c. Isocyanate group-containing compounds (b3) The isocyanate group-containing compound (b3) is not particularly limited as long as it is a compound having two or more isocyanate groups in the molecule.
[0092] Specific examples of isocyanate group-containing compounds having two isocyanate groups in one molecule include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisine diisocyanate, 2,4,6-triisocyanate toluene, 2,4,6-triisocyanate toluene, 2,4,6-triisocyanate toluene, 2,4,6-triisocyanate toluene, dianisine diisocyanate ... Aromatic diisocyanates such as ethylene diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate, trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexyl Aliphatic diisocyanates such as samethylene diisocyanate, ω,ω'-diisocyanato-1,3-dimethylbenzene, ω,ω'-diisocyanato-1,4-dimethylbenzene, ω,ω'-diisocyanato-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, 1,3-tetramethylxylylene diisocyanate, and other aromatic aliphatic diisocyanates, 3-isocyanatomethyl-3,5,5-trimethylcyclohexyl isocyanate [also known as isophorone], alicyclic diisocyanates such as 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), 1,3-bis(isocyanatomethyl)cyclohexane, and 1,4-bis(isocyanatomethyl)cyclohexane.
[0093] Furthermore, examples of the isocyanate group-containing compound having three isocyanate groups in one molecule include aromatic polyisocyanates, aliphatic polyisocyanates such as lysine triisocyanate, aromatic aliphatic polyisocyanates, and alicyclic polyisocyanates, and also include the above-described trimethylolpropane adducts of diisocyanates, biuret products reacted with water, and trimers having an isocyanurate ring.
[0094] The isocyanate group-containing compound may be a blocked isocyanate group-containing compound in which the isocyanate group in the various isocyanate group-containing compounds exemplified above is protected with ε-caprolactam, MEK oxime, or the like. Specific examples include compounds in which the isocyanate group of the isocyanate group-containing compound is blocked with ε-caprolactam, methyl ethyl ketone (hereinafter referred to as MEK) oxime, cyclohexanone oxime, pyrazole, phenol, or the like. In particular, when a hexamethylene diisocyanate trimer having an isocyanurate ring and blocked with MEK oxime or pyrazole is used in the present invention, it is highly preferred because it has excellent adhesive strength to polyimide and copper and excellent heat resistance. Furthermore, from the viewpoint of heat resistance, it is preferable for the compound to have three or more isocyanate groups.
[0095] 1-2-d. Metal chelate compounds (b4) The metal chelate compound (b4) is an organometallic compound consisting of a metal and an organic substance, which reacts with the reactive functional group of the polyimide resin (A) or the crosslinkable functional group of the crosslinking agent (B) to form a crosslink. The type of organometallic compound is not particularly limited, but examples include organoaluminum compounds, organotitanium compounds, and organozirconium compounds. The bond between the metal and the organic substance may be a metal-oxygen bond, but is not limited to a metal-carbon bond. Furthermore, from the viewpoint of heat resistance, it is preferable that the number of functional groups (the number of groups capable of forming coordinate bonds) be 3 or more.
[0096] The organoaluminum compound is preferably an aluminum metal chelate compound. Examples of the aluminum metal chelate compound include ethyl acetoacetate aluminum diisopropylate, aluminum tris(ethyl acetoacetate), alkyl acetoacetate aluminum diisopropylate, aluminum monoacetylacetonate bis(ethyl acetoacetate), aluminum tris(acetylacetate), aluminum monoacetylacetate bis(ethyl acetoacetate), aluminum di-n-butoxide monomethyl acetoacetate, aluminum diisobutoxide monomethyl acetoacetate, aluminum di-sec-butoxide monomethyl acetoacetate, aluminum isopropylate, monosec-butoxyaluminum diisopropylate, aluminum sec-butylate, and aluminum ethylate.
[0097] The organic titanium compound is preferably a titanium metal chelate compound. Examples of titanium metal chelate compounds include titanium acetylacetonate, titanium tetraacetylacetonate, titanium ethylacetoacetate, titanium octylene glycolate, titanium ethylacetoacetate, titanium-1,3-propanedioxybis(ethylacetoacetate), polytitanium acetylacetonate, tetraisopropyl titanate, tetra-normal butyl titanate, butyl titanate dimer, tetraoctyl titanate, diamyl titanate, tetratertiary butyl titanate, tetrastearyl titanate, titanium isostearate, tri-n-butoxytitanium monostearate, di-i-propoxytitanium distearate, titanium stearate, di-i-propoxytitanium diisostearate, (2-n-butoxycarbonylbenzoyloxy)tributoxytitanium, etc. The organic zirconium compound is preferably a zirconium metal chelate compound. Examples of the zirconium metal chelate compound include zirconium tetraacetylacetonate, zirconium tributoxyacetylacetonate, zirconium monobutoxyacetylacetonate bis(ethylacetoacetate), zirconium dibutoxybis(ethylacetoacetate), zirconium tetraacetylacetonate, normal propyl zirconate, normal butyl zirconate, zirconium stearate, and zirconium octylate. Among these, organic titanium compounds and organic zirconium compounds are preferred in terms of thermosetting reactivity.
[0098] 1-2-e. Carbodiimide group-containing compound (b5) The carbodiimide group-containing compound (b5) is not particularly limited as long as it has two or more carbodiimide groups in the molecule. Examples of the carbodiimide group-containing compound include Carbodilite V-01, V-03, V-05, V-07, and V-09 (Nisshinbo Chemical Inc.), and cyclic carbodiimide (Teijin Limited). From the viewpoint of heat resistance, compounds having an average of three or more carbodiimide groups in one molecule are preferred.
[0099] 1-2-f. Maleimide group-containing compound (b6) The maleimide group-containing compound (b6) is not particularly limited as long as it is a compound having two or more maleimide groups in the molecule, but it is more preferable that the average number of functional groups is three or more. Specific examples include o-phenylene bismaleimide, m-phenylene bismaleimide, p-phenylene bismaleimide, 4-methyl-1,3-phenylene bismaleimide, N,N'-(toluene-2,6-diyl)bismaleimide, 4,4'-diphenylmethane bismaleimide, bisphenol A diphenyl ether bismaleimide, 3,3'-dimethyl-5,5'-diethyl-4,4'-diphenylmethane bismaleimide, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenylsulfone bismaleimide, and 1,3-bis(3-maleimide). (phenoxy)benzene, 1,3-bis(4-maleimidophenoxy)benzene, polyphenylmethane maleimide (CAS NO: 67784-74-1, reaction product of polymer of formaldehyde and aniline with maleic anhydride), N,N'-ethylene bismaleimide, N,N'-trimethylene bismaleimide, N,N'-propylene bismaleimide, N,N'-tetramethylene bismaleimide, N,N'-pentamethylene bismaleimide, N,N'-(1,3-pentanediyl)bis(maleinimide), N,N'-hexamethylene bismaleimide, N,N '-(1,7-heptanediyl)bismaleimide, N,N'-(1,8-octanediyl)bismaleimide, N,N'-(1,9-notanediyl)bismaleimide, N,N'-(1,10-decanediyl)bismaleimide, N,N'-(1,11-undecanediyl)bismaleimide, N,N'-(1,12-dodecanediyl)bismaleimide, N,N'-[(1,4-phenylene)bismethylene]bismaleimide, N,N'-[(1,2-phenylene)bismethylene]bismaleimide, N,N'-[(1,3-phenylene)bismethylene]bismaleimide , 1,6'-bismaleimido-(2,2,4-trimethyl)hexane, N,N'-[(methylimino)bis(4,1-phenylene)]bismaleimide, N,N'-(2-hydroxypropane-1,3-diylbisiminobiscarbonylbisethylene)bismaleimide, N,N'-(dithiobisethylene)bismaleimide, N,N'-[hexamethylenebis(iminocarbonylmethylene)]bismaleimide, N,N'-carbonylbis(1,4-phenylene)bismaleimide, N,N',N''-[nitrilotris(ethylene)]trismaleimide, N,N',N''-[nitrilotris(4,1-phenylene)]trismaleimide, N,N'-[p-phenylenebis(oxy-p-phenylene)]bismaleimide, N,N'-[methylenebis(oxy)bis(2-methyl-1,4-phenylene)]bismaleimide, N,N'-[methylenebis(oxy-p-phenylene)]bis(maleimide), N,N'-[dimethylsilylenebis[(4,1-phenylene)(1,3,4-oxadiazole-5,2-diyl)(4,1-phenylene)]]bismaleimide, N,N'-[(1,3-phenylene)bisoxy bis(3,1-phenylene)]bismaleimide, 1,1'-[3'-oxospiro[9H-xanthene-9,1'(3'H)-isobenzofuran]-3,6-diyl]bis(1H-pyrrole-2,5-dione), N,N'-(3,3'-dichlorobiphenyl-4,4'-diyl)bismaleimide, N,N'-(3,3'-dimethylbiphenyl-4,4'-diyl)bismaleimide, N,N'-(3,3'-dimethoxybiphenyl-4,4'-diyl)bismaleimide, N,N'-[methylenebis(2-ethyl-4,1-phenylene)]bismaleimide, N,N'-[methylenebis(2,6-diethyl-4,1-phenylene)]bismaleimide, N,N'-[methylenebis(2-bromo-6-ethyl-4,1-phenylene)]bismaleimide, N,N'-[methylenebis(2-methyl-4,1-phenylene)]bismaleimide, N,N'-[ethylenebis(oxyethylene)]bismaleimide, N,N'-[sulfonylbis(4,1-phenylene)bis(oxy)bis(4,1-phenylene)]bismaleimide, N,N'-[naphthalene-2,7-diylbis(oxy)bis(4,1-phenylene)]bis Maleimide, N,N'-[p-phenylenebis(oxy-p-phenylene)]bismaleimide, N,N'-[(1,3-phenylene)bisoxybis(3,1-phenylene)]bismaleimide, N,N'-(3,6,9-trioxaundecane-1,11-diyl)bismaleimide, N,N'-[isopropylidenebis[p-phenyleneoxycarbonyl(m-phenylene)]]bismaleimide, N,N'-[isopropylidenebis[p-phenyleneoxycarbonyl(p-phenylene)]]bismaleimide, N,N'-[isopropylidenebis[(2,6-dichlorobenzene-4,1-diyl)oxycarbonyl(p-phenylene)]]bismaleimide, N,N'-[(phenylimino)bis(4,1-phenylene)]bismaleimide, N,N'-[azobis(4,1-phenylene)]bismaleimide, N,N'-[1,3,4-oxadiazole-2,5-diylbis(4,1-phenylene)]bismaleimide, 2,6-bis[4-(maleimido-N-yl)phenoxy]benzonitrile, N,N'-[1,3,4-oxadiazole-2,5-diylbis(3 ,1-phenylene)]bismaleimide, N,N'-[bis[9-oxo-9H-9-phospha(V)-10-oxaphenanthrene-9-yl]methylenebis(p-phenylene)]bismaleimide, N,N'-[hexafluoroisopropylidenebis[p-phenyleneoxycarbonyl(m-phenylene)]]bismaleimide, N,N'-[carbonylbis[(4,1-phenylene)thio(4,1-phenylene)]]bismaleimide, N,N'-carbonylbis(p-phenyleneoxyp-phenylene)bismaleimide , N,N'-[5-tert-butyl-1,3-phenylenebis[(1,3,4-oxadiazole-5,2-diyl)(4,1-phenylene)]]bismaleimide, N,N'-[cyclohexylidenebis(4,1-phenylene)]bismaleimide, N,N'-[methylenebis(oxy)bis(2-methyl-1,4-phenylene)]bismaleimide, N,N'-[5-[2-[5-(dimethylamino)-1-naphthylsulfonylamino]ethylcarbamoyl]-1,3-phenylene]bismaleimide, N,N'-(oxadiazole-5,2-diyl)-1,3-phenylene Examples of polyfunctional maleimides include N,N'-[dithiobis(ethylene)]bismaleimide, N,N'-[dithiobis(m-phenylene)]bismaleimide, N,N'-(3,6,9-trioxaundecane-1,11-diyl)bismaleimide, N,N'-(ethylenebis-p-phenylene)bismaleimide, BMI-689, BMI-1500, BMI-1700, BMI-3000, BMI-5000, and BMI-9000 manufactured by Designer Molecules, and ODA-BMI and BAFBMI manufactured by JFE Chemical Corporation.
[0100] Further, polyfunctional maleimides obtained by reacting polyfunctional amines with maleic anhydride can be used. Examples of polyfunctional amines include isophoronediamine, dicyclohexylmethane-4,4'-diamine, and Huntsman Corporation's Jeffamine D-230, HK-511, D-400, XTJ-582, D-2000, XTJ-578, XTJ-509, XTJ-510, T-403, and T-5000, which have terminally aminated polypropylene glycol backbones; XTJ-500, XTJ-501, XTJ-502, XTJ-504, XTJ-511, XTJ-512, and XTJ-590, which have terminally aminated ethylene glycol backbones; and XTJ-542, XTJ-533, XTJ-536, XTJ-548, and XTJ-559, which have terminally aminated polytetramethylene glycol backbones.
[0101] When the maleimide group-containing compound (b6) is crosslinked by radicals, a radical polymerization initiator can be added. Specific examples include azo compounds and organic peroxides. The polymerization initiators can be used alone or in combination of two or more. Examples of azo compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]. Examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butylperoxy 2-ethylhexanoate, t-butylperoxyneodecanoate, t-butylperoxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.
[0102] 1-3. Ultraviolet absorber (C) The composition may optionally contain an ultraviolet absorber (C). The ultraviolet absorber absorbs ultraviolet light and converts the ultraviolet light energy into thermal energy. When UV laser light is used to form vias in a cured layer obtained by curing a thermosetting sheet such as an adhesive sheet formed from the composition, the addition of an ultraviolet absorber can adjust the amount of energy applied to the adhesive sheet or cured layer. As a result, laser processability can be improved. The ultraviolet absorber (C) is preferably contained in an amount of 0.1 to 10 mass% of the composition, more preferably 0.1 to 5 mass%. The adhesive sheet or cured layer can be irradiated with laser light of various wavelengths (ultraviolet light, infrared light, etc.) depending on the application. Multiple laser beams may be used as needed.
[0103] The ultraviolet absorber (C) may be a benzophenone, benzotriazole, triazine, salicylic acid ester, or cyanoacrylate. Zinc oxide may also be used. The ultraviolet absorber (C) may be used regardless of whether or not the surface has been treated. Specifically, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-methoxy-2'-carboxybenzophenone, 2-hydroxy-4-octoxybenzophenone, 2-hydroxy-4-n-dodecyloxybenzophenone, 2-hydroxy-4-n-octadecyloxybenzophenone, 2-hydroxy-4-benzyloxybenzophenone, 2-hydroxy-4-methoxy-5-sulfobenzophenone, 2-hydroxy-5-chlorobenzophenone, 2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, poly-4-(2-acryloxyethoxy)-2-hydroxybenzophenone, 2-(2-hydroxy-5-methylphenyl)benzotriazole, 2-(2-hydroxy-5-t-butylphenyl)benzotriazole, 2-(2-hydroxy-5-tert-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dimethylphenyl)benzotriazole, 2-(2-methyl-4-hydroxyphenyl)benzotriazole, 2-(2-hydroxy-3-methyl-5-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-di-t-butylphenyl)benzotriazole, 2-(2-hydroxy-3,5-dimethylphenyl)-5-methoxybenzotriazole, 2-(2-hydroxy-3-t-butyl-5-methylphenyl)-5-chlor Examples of suitable esters include chlorobenzotriazole, 2-(2-hydroxy-5-t-butylphenyl)-5-chlorobenzotriazole, 2-[4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl]-5-(octyloxy)phenol, 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-(hexyloxy)phenol, phenyl salicylate, p-octylphenyl salicylate, ethyl 2-cyano-3,3-diphenylacrylate, 2-ethylhexyl 2-cyano-3,3-diphenylacrylate, and 2,2-bis{[2-cyano-3,3-diphenylacryloyloxy]methyl}propane-1,3-diyl-bis(2-cyano-3,3-diphenylacrylate).
[0104] 1-4. Filler (D) The composition may contain a filler (D) as an optional component. From the viewpoint of improving the plating solution resistance of the composition, its insulating reliability after a heat cycle test, and its lamination properties to LCP, the composition preferably contains 3 to 60 mass% of filler (D), more preferably 5 to 40 mass% of filler (D), based on 100 mass% of the composition. By using a filler (D) content of 3 mass% or more, the occurrence of cracking, peeling, and other defects due to stress caused by sudden temperature changes during a heat cycle test can be effectively suppressed. Furthermore, by including a specific amount or more of a component that is resistant to corrosion by the plating solution, the occurrence of cracking, peeling, and other defects due to stress caused by sudden temperature changes during a heat cycle test can be effectively suppressed, thereby preventing the intrusion of moisture into cracked or peeled areas and improving insulation reliability. On the other hand, by using a filler (D) content of 60 mass% or less, the proportion of resin components that contribute to adhesion to the adherend is increased, resulting in better lamination properties to LCP substrates.
[0105] The shape of the filler (D) is not particularly limited. Examples include spherical, powdery, fibrous, needle-like, and scale-like shapes. Specific examples of the filler (D) include fluorine fillers: polytetrafluoroethylene powder and modified products thereof, tetrafluoroethylene-perfluoroalkyl vinyl ether powder, tetrafluoroethylene-ethylene powder, tetrafluoroethylene-hexafluoropropylene powder, tetrafluoroethylene-vinylidene fluoride powder, tetrafluoroethylene-hexafluoropropylene-perfluoroalkyl vinyl ether powder, polychlorotrifluoroethylene powder, chlorotrifluoroethylene-ethylene powder, chlorotrifluoroethylene-vinylidene fluoride powder, polyvinylidene fluoride powder, and polyvinyl fluoride powder.Further, polyethylene powder, polyacrylate powder, epoxy resin powder, polyamide powder, polyimide powder, polyurethane powder, liquid crystal polymer beads, polysiloxane powder, etc., as well as polymer fillers such as multilayer core-shell structures using silicone, acrylic, styrene butadiene rubber, butadiene rubber, etc.; (poly)phosphate compounds such as melamine phosphate, melamine polyphosphate, guanidine phosphate, guanidine polyphosphate, ammonium phosphate, ammonium polyphosphate, ammonium amide phosphate, ammonium amide polyphosphate, carbamate phosphate, and carbamate polyphosphate; organic phosphate ester compounds, phosphazene compounds, phosphonic acid compounds, phosphinic acid compounds such as aluminum diethylphosphinate, aluminum methylethylphosphinate, aluminum diphenylphosphinate, aluminum ethylbutylphosphinate, aluminum methylbutylphosphinate, and aluminum polyethylenephosphinate; phosphine oxide compounds, phosphorane compounds, phosphinic acid compounds, etc. Examples of fillers include phosphorus-based fillers such as sulfonamide compounds; nitrogen-based fillers such as benzoguanamine, melamine, melam, melem, melon, melamine cyanurate, cyanuric acid compounds, isocyanuric acid compounds, triazole-based compounds, tetrazole compounds, diazo compounds, and urea; and inorganic fillers such as crystalline silica, amorphous silica, hollow silica, porous silica, mica, talc, kaolin, clay, hydrotalcite, wollastonite, xonotlite, silicon nitride, boron nitride, aluminum nitride, calcium hydrogen phosphate, calcium phosphate, glass flakes, hydrated glass, calcium titanate, sepiolite, magnesium sulfate, aluminum hydroxide, magnesium hydroxide, zirconium hydroxide, barium hydroxide, calcium hydroxide, titanium oxide, tin oxide, aluminum oxide, magnesium oxide, zirconium oxide, zinc oxide, molybdenum oxide, antimony oxide, nickel oxide, zinc carbonate, magnesium carbonate, calcium carbonate, barium carbonate, zinc borate, and aluminum borate.
[0106] When a cured layer formed from the present composition is applied to an insulating layer of a large-capacity, high-speed substrate, examples of the insulating layer include liquid crystal polymers, fluororesins, modified polyphenylene ethers, glass balloons which are hollow glass bodies, hollow coal ash bodies, shirasu balloons, calcium carbonate, talc, and mixtures thereof.
[0107] From the viewpoint of impact absorption, it is preferable to use fluorine filler, boron nitride, liquid crystal polymer and silica. The filler (D) can be used alone or in combination of two or more.
[0108] The method for adding the filler (D) is not particularly limited, and any conventionally known method can be used. Suitable examples include adding the filler to a polymerization reaction solution before or during the polymerization of the polyimide resin (A), kneading the filler into the polyimide resin (A) using a three-roll mill, or preparing a dispersion containing the filler and mixing it with the polyimide resin (A). Furthermore, to disperse the filler well and stabilize the dispersion, dispersants, thickeners, etc. can also be used within a range that does not affect the physical properties of the thermosetting resin composition.
[0109] 1-5.Other optional ingredients The composition may contain various additives within the scope of the present invention. For example, polyimide resins other than polyimide resin (A) may be used. Any thermoplastic resin may also be used. A catalyst may be added as an optional component to promote crosslinking between the phenolic hydroxyl groups in polyimide resin (A) and crosslinking agent (B). Suitable catalysts include imidazole-based, amine-based, and phosphorus-based catalysts. Other examples of additives include dyes, pigments (e.g., carbon black), flame retardants, antioxidants, polymerization inhibitors, defoamers, leveling agents, ion scavengers, moisturizers, viscosity modifiers, preservatives, antibacterial agents, antistatic agents, antiblocking agents, ultraviolet absorbers, infrared absorbers, and electromagnetic wave shielding agents.
[0110] 1-6. Characteristics of thermosetting compositions From the viewpoint of insulation reliability after a heat cycle test, the present composition preferably has a glass transition temperature in the range of 0 to 70°C after thermal curing at 180°C for 60 minutes. It is more preferably 10 to 60°C. Having a glass transition temperature of 0°C or higher prevents significant collapse of the crosslinked structure in the composition even with extreme environmental temperature cycles, thereby suppressing the flow of metal ions generated from electrodes that cause short-circuiting, resulting in excellent insulation reliability. On the other hand, having a glass transition temperature of 70°C or lower imparts a certain degree of flexibility to the present composition, thereby reducing stress in response to the expansion and contraction of the adherend during extreme environmental temperature cycles, thereby preventing peeling and preventing short-circuiting caused by moisture entering through gaps resulting from peeling. The above curing conditions are used to estimate the Tg of the present composition during the curing process and do not in any way limit the curing conditions for the cured product formed from the present composition.
[0111] 2. Method for producing thermosetting composition The present composition is obtained by blending the various components. Instead of a polyimide precursor, an imidized polyimide resin (A) is used as a blending component. A solvent can be used as appropriate during blending. The solid content can be, for example, 20 to 60 mass %. The polyimide resin (A) of this embodiment has a dimer structure, and therefore can be easily dissolved in various organic solvents.
[0112] The composition can be in the form of, for example, powder, film, sheet, plate, pellet, paste, or liquid. A liquid or paste thermosetting composition can be easily obtained by adjusting the viscosity using a solvent. A film, sheet, or plate thermosetting composition can be formed, for example, by applying a liquid or paste thermosetting composition and drying it. A powder or pellet thermosetting composition can be obtained, for example, by pulverizing or cutting the film-like or other thermosetting composition into a desired size.
[0113] An adhesive sheet can be obtained, for example, by applying a coating solution of the present composition containing a solvent to one side of a release film, and then removing the liquid medium, such as an organic solvent, and drying, for example, at 40 to 150°C. A double-sided release film adhesive sheet can be obtained by laminating another release film on the surface of the resulting adhesive sheet. Laminating both sides with release films can prevent surface contamination of the adhesive sheet. The adhesive sheet can be isolated by peeling off the release film. The two release films can be the same or different types. Using release films with different release properties allows for varying levels of release force, making it easier to peel them off in order. Alternatively, an adhesive sheet can be formed by directly applying the coating solution to a substrate.
[0114] Examples of the substrate include resin materials such as polyimide film, polyethylene film, polycarbonate, polyethylene, liquid crystal polymer, phenolic resin, and aramid resin; metal materials such as copper, aluminum, and stainless steel; inorganic materials such as ITO, glass, silicon, and silicon carbide; and composite materials in which any of these materials are combined. This composition has a storage modulus G' of 1.0 x 10 7 The soft polyimide resin (A) having a Pa temperature of 30 to 90°C not only has excellent adhesion to various substrates but also has excellent moldability.
[0115] The coating method can be selected from known methods such as comma coating, knife coating, die coating, lip coating, roll coating, curtain coating, bar coating, gravure printing, flexographic printing, screen printing, dip coating, spray coating, and spin coating.
[0116] The thickness of the adhesive sheet after drying is preferably 5 to 500 μm, more preferably 10 to 100 μm, in order to ensure sufficient adhesiveness and ease of handling.
[0117] 3. Manufacturing method of the cured product A cured product can be obtained by subjecting this composition to a heat curing treatment. For example, a method can be exemplified in which the thermosetting composition is molded into a desired shape such as a sheet and then heat cured. A molded product such as a sheet of the thermosetting composition can be easily obtained by applying a thermosetting composition containing a solvent and drying it. The molded product is then heat cured to form a cured product. The molding and curing may occur simultaneously. The sheet-shaped cured product is also called a cured layer.
[0118] The heat curing temperature may be appropriately selected depending on the type of crosslinking agent (B). For example, a method of heat treatment at a temperature of 150 to 230°C for 30 to 180 minutes can be exemplified. During heat curing, pressure can be applied (for example, 5 MPa) for thermocompression bonding, if necessary. By the heat curing treatment, a crosslinked structure is formed in the composition, and a three-dimensionally crosslinked cured product is obtained.
[0119] 4. Uses of thermosetting compositions and cured products The present composition exhibits excellent lamination properties with LCP substrates, making it suitable as an adhesive sheet for flexible printed wiring boards, which require low dielectric properties. Its excellent adhesive properties after curing make it suitable as an adhesive sheet or bonding material for bonding various materials (e.g., resin layers, metal layers, inorganic layers such as ITO, composite layers, etc.). For example, it is suitable as an adhesive sheet for copper-clad laminates and as a bonding material for components such as electronic circuit boards and electronic components. Copper-clad laminates (CCLs) require a process of electrolytic copper plating on the copper foil surface, followed by etching with an alkaline or other plating solution after removing the resist layer. The present cured product exhibits excellent plating solution resistance, making it suitable as an adhesive sheet for copper-clad laminates. Furthermore, the present cured product exhibits excellent laser processability, making it suitable for applications involving the formation of openings such as vias and patterns. It can also be used as an adhesive layer for carrier tapes for TBA tapes and COF tapes.
[0120] Furthermore, the polyimide resin (A) of this composition has excellent electrical insulating properties, and therefore can provide a cured product with excellent insulating properties. For example, it is suitable for use as a material for forming an insulating layer on a circuit board (including a coverlay layer for a printed wiring board, an interlayer insulating layer for a built-up board, a bonding sheet, etc.). It is also suitable for use as an insulating member for electronic components. Examples of electronic components include power modules such as power semiconductor devices, LEDs, and inverter devices, and it is suitable for use as an insulating layer for substrates, semiconductor chip packages, underfill materials, adhesives, etc. It can also be used as a thermosetting composition for copper-clad laminates, a bonding sheet for forming a wiring board, a cover coat for flexible substrates, a prepreg, etc.
[0121] By incorporating a conductive filler as filler (D), the composition may be used as a conductive adhesive sheet. Furthermore, by using a thermally conductive filler as filler (D), the composition can be used in a wide range of applications requiring heat dissipation. For example, by utilizing the moldability of the resin composition, the composition can be suitably used as a heat dissipation component of a desired shape. It is particularly useful as a heat dissipation adhesive or heat dissipation sheet for battery exterior materials and for electronic devices (smartphones, tablet devices, etc.) that cannot be equipped with fans or heat sinks due to their small size and lightness. Furthermore, the cured product of the composition is suitable as an adhesive layer between a heat generating element and a heat sink or as a heat spreader. It can also be used as a heat dissipation layer that covers one or more electronic components mounted on a substrate.
[0122] 5. Printed wiring boards Because the adhesive sheet made from this composition has the above-mentioned properties, it can be suitably used in the production of printed wiring boards. The adhesive sheet functions as a cured layer that exhibits adhesive properties upon thermal curing. Furthermore, the cured layer, which is the cured product of the thermosetting sheet formed from this composition, has excellent insulating properties, making it suitable for use as a protective film or interlayer insulating layer in printed wiring boards. Because the thermosetting sheet made from this composition uses a highly flexible polyimide resin (A), it can be laminated at low temperatures in a short time. Therefore, it is suitable for bonding to liquid crystal polymer (LCP) substrates, which have excellent low dielectric properties.
[0123] Printed wiring boards can be manufactured, for example, by processing the copper foil in a copper-clad laminate by etching or the like, forming a signal circuit or the like on the resulting substrate, laminating the resulting substrate and cover film via an adhesive sheet, and bonding them by thermosetting. Flexible printed wiring boards can also be manufactured, for example, by forming a conductor pattern on an insulating flexible film, forming a protective film on top of the conductor pattern via the adhesive sheet, and thermocompression bonding. Examples of flexible films include polyester, polyimide, liquid crystal polymer, and PTFE film. Conductive patterns can be formed by printing techniques, sputtering, or plating.
[0124] A via hole may be formed in the cured layer of the composition formed on one or both sides of a printed wiring board by drilling or laser processing, and then filled with a conductive agent. Alternatively, a circuit layer may be formed on an interlayer insulating layer formed from the cured product of the composition. The cured product of the composition has excellent plating resistance, making it suitable for the manufacture of multilayer printed wiring boards. Furthermore, the crosslinking structure between the highly flexible polyimide resin (A) and the crosslinking agent (B) via phenolic hydroxyl groups reduces residual stress and ensures excellent insulation reliability after heat cycle testing. Printed wiring boards formed using the composition have excellent insulation reliability over a wide temperature range, making them suitable for various electronic devices such as smartphones and tablet devices. [Example]
[0125] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples as long as it does not deviate from the spirit of the present invention. Unless otherwise specified, "%" and "parts" are based on mass.
[0126] (i) Measurement of weight average molecular weight (Mw) Mw was measured using a Showa Denko GPC (gel permeation chromatography) "GPC-101." The solvent was THF (tetrahydrofuran), and two "KF-805L" (Showa Denko GPC column: 8 mm ID x 300 mm size) columns connected in series were used. The sample concentration was 1% by mass, the flow rate was 1.0 mL / min, the pressure was 3.8 MPa, and the column temperature was 40°C. Mw was determined in polystyrene equivalent terms. Data analysis was performed using the manufacturer's built-in software to calculate the calibration curve, molecular weight, and peak area, and Mw was calculated for the retention time range of 17.9 to 30.0 minutes.
[0127] (ii) Acid value measurement The acid value was measured in accordance with JIS K0070. Specifically, approximately 1 g of sample (polyimide resin (A)) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve it. Phenolphthalein test solution was added as an indicator, and the solution was titrated with 0.1 N alcoholic potassium hydroxide solution. The endpoint was determined when the indicator retained a pale pink color for 30 seconds. The acid value was calculated using the following formula. Acid value (mgKOH / g)=(5.611×a×F) / S however, S: Amount of sample collected (g) a: Amount of 0.1N alcoholic potassium hydroxide solution consumed (mL) F: Potency of 0.1N alcoholic potassium hydroxide solution
[0128] (iii) Measurement of phenolic hydroxyl value The phenolic hydroxyl value was measured in accordance with JIS K0070. The phenolic hydroxyl value is expressed as the amount (mg) of potassium hydroxide required to neutralize the acetic acid bonded to the phenolic hydroxyl groups when the phenolic hydroxyl groups contained in 1 g of polyimide resin (A) are acetylated. The phenolic hydroxyl value of polyimide resin (A) was calculated taking into account the acid value, as shown in the following formula. Specifically, approximately 1 g of sample (polyimide resin (A)) was precisely weighed into a stoppered Erlenmeyer flask and dissolved in 100 mL of cyclohexanone solvent. Exactly 5 mL of the acetylating agent (a solution prepared by dissolving 25 g of acetic anhydride in pyridine to a volume of 100 mL) was then added and stirred for approximately 1 hour. Phenolphthalein test solution was added as an indicator and allowed to stand for 30 seconds. The solution was then titrated with 0.5 N alcoholic potassium hydroxide solution until it turned a pale pink color. The phenolic hydroxyl value was calculated using the following formula. Phenolic hydroxyl value (mgKOH / g) = [{(ba) × F × 28.05} / S] + D however, S: Amount of sample collected (g) a: Consumption of 0.5N alcoholic potassium hydroxide solution (mL) b: Amount of 0.5N alcoholic potassium hydroxide solution consumed in the blank experiment (mL) F: Potency of 0.5N alcoholic potassium hydroxide solution D: Acid value (mgKOH / g) The side chain phenolic hydroxyl value was calculated from the ratio of the monomers used in the synthesis of polyimide resin (A) to the obtained phenolic hydroxyl value. The terminal phenolic hydroxyl value was calculated by subtracting the side chain phenolic hydroxyl value from the experimentally obtained phenolic hydroxyl value. The value of b was determined by titrating 5 mL of the acetylating agent (a 100 mL solution of 25 g of acetic anhydride dissolved in pyridine) with 0.5 N alcoholic potassium hydroxide solution.
[0129] (iv) Amine value determination Approximately 1 g of sample (polyimide resin (A)) was precisely weighed and placed in a stoppered Erlenmeyer flask, and 100 mL of cyclohexanone solvent was added to dissolve the sample. A few drops of an indicator prepared separately by mixing 0.20 g of Methyl Orange dissolved in 50 mL of distilled water with 0.28 g of Xylene Cyanol FF dissolved in 50 mL of methanol was added and the mixture was left to stand for 30 seconds. The solution was then titrated with 0.1 N alcoholic hydrochloric acid solution until it turned blue-gray. The amine value was calculated using the following formula: Amine number (mgKOH / g) = (5.611 x a x F) / S however, S: Amount of sample collected (g) a: Consumption volume of 0.1N alcoholic hydrochloric acid solution (mL) F: Potency of 0.1N alcoholic hydrochloric acid solution
[0130] (v) Determination of acid anhydride value Approximately 1 g of sample (polyimide resin (A)) was precisely weighed into a stoppered Erlenmeyer flask and dissolved in 100 mL of 1,4-dioxane solvent. 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio by mass: 1.49 / 800 / 80) was added, in an amount greater than the amount of acid anhydride groups in the sample, and the mixture was stirred for 15 minutes to react with the acid anhydride groups. The excess octylamine was then titrated with a mixed solution of 0.02 M perchloric acid and 1,4-dioxane. A blank measurement was also conducted using 10 mL of a mixed solution of octylamine, 1,4-dioxane, and water (mixing ratio by mass: 1.49 / 800 / 80) without sample. The acid anhydride value was calculated using the following formula (unit: mgKOH / g): Acid anhydride value (mgKOH / g) = 0.02 × (BA) × F × 56.11 / S B: Blank titer (mL) A: Titration volume of sample (mL) S: Amount of sample collected (g) F: Potency of 0.02 mol / L perchloric acid
[0131] (vi) Measurement of storage modulus G' and Tg of polyimide resin (A) Polyimide resin (A) according to each synthesis example was dissolved in cyclohexanone to a nonvolatile content of 35% to prepare a polyimide resin varnish. The varnish was applied to a heat-resistant release film using a doctor blade with a 10 mil gap and dried at 130°C for 10 minutes to obtain a 25 μm-thick resin sheet. The resulting resin sheet was peeled from the heavy release film, and the storage modulus and Tg of the resin sheet were measured using a dynamic viscoelasticity analyzer "DVA200" (manufactured by IT Measurement & Control Co., Ltd.). The storage modulus was measured by cooling the resin sheet to 0°C, then raising the temperature to 300°C at a rate of 10°C / min, and measuring the viscoelasticity at a vibration frequency of 10 Hz and a grip length of 10 mm. The storage modulus G' was 1.0 x 10 7 The temperature at which the tangent length of the tangential ... Heating rate: 10℃ / min Measurement frequency: 10Hz Grip length: 10 mm Width: 5mm
[0132] (vii) Measurement of Tg when the thermosetting composition is heat-treated at 180°C for 60 minutes A polyimide resin sheet was obtained by the same method as in (vi) above. The polyimide resin sheet was then heat-treated at 180°C for 60 minutes to obtain a cured sheet. The loss tangent (tanδ) of the obtained cured sheet was measured in the temperature range of -50 to 200°C using the same dynamic viscoelasticity measuring device as in (vi) under the same conditions of heating rate, measuring frequency, grip length, and width, and Tg was measured by the same method as above.
[0133] <Synthesis of polyimide resin> [Synthesis Example 1] Polyimide resin (P1) A 1-L separable flask equipped with an oil bath and a stirrer was charged with nitrogen gas. 200 g of cyclohexanone was added, followed by 149.8 g of dimer diamine (PRIAMINE 1075) as a diamine and 4.7 g of m-aminophenol as a monoamine compound, with stirring. 67.3 g of 1,2,4,5-cyclohexanetetracarboxylic dianhydride as a tetracarboxylic dianhydride was then added and stirred at room temperature for 30 minutes. The mixture was heated to 100 °C and stirred for 3 hours. After that, the oil bath was removed and the mixture was returned to room temperature to obtain a varnish-like polyimide precursor. The mixture was then heated at 170 °C for 10 hours while removing the distilled water using a Dean-Stark trap. The polyimide resin (P1) was imidized. The Mw, Tg, and functional value of the resulting polyimide resin are shown in Table 1.
[0134] [Synthesis Examples 2 to 22, Comparative Synthesis Examples 1 to 4] Polyimide Resins (P2) to (P26) Polyimide resins P2 to P26 were obtained in the same manner as in Synthesis Example 1, except that the monomers shown in Tables 1 and 2 were used. The meanings of the abbreviations in Table 1 etc. are shown below. TA1: 1,2,4,5-cyclohexanetetracarboxylic dianhydride TA2: 1,2,3,4-butanetetracarboxylic dianhydride TA3: 4,4'-(4,4'-isopropylidenediphenoxy)diphthalic anhydride TA4: 4-(2,5-dioxotetrahydrofuran-3-yl)-1,2,3,4-tetrahydronaphthalene-1,2-dicarboxylic acid anhydride DA1: Priamine 1075 (dimer diamine) DA2: 4,4'-(hexafluoroisopropylidene)bis(2-aminophenol) DA3: 1,12-dodecanediamine MA1: m-aminophenol MA2: o-aminophenol MA3: p-aminophenol MA4: 4-hydroxyphenethylamine (tyramine)
[0135] Tables 1 and 2 show the blending amount (parts by mass) of the polyimide resin in each synthesis example, the acid anhydride group value, phenolic hydroxyl group (hereinafter also referred to as PhOH) value (side chain PhOH value, terminal PhOH value), amine value, Mw, PhOH value / total functional group value, etc. of the obtained polyimide resin. 1 X relative to 100 mol% of residues 1 mole % of a residues, X 2 X relative to 100% by mass of the monomer (charged amount) to obtain the residue 2 The mass % of the monomer (charged amount) required to obtain d is shown. In this specification, the total functional group value refers to the total functional group value of the amino group value, acid anhydride group value, and phenolic hydroxyl group value.
[0136] [Table 1]
[0137] [Table 2]
[0138] Details of the materials used in the examples and comparative examples are shown below. (Crosslinking agent (B)) (B)-1: Epoxy group-containing compound (b1), Denacol EX-614B (manufactured by Nagase ChemteX Corporation, sorbitol polyglycidyl ether, tetrafunctional, functional group equivalent weight 173 g / eq.) (B)-2: Cyanate ester compound (b2), BAD (manufactured by Mitsubishi Gas Chemical Company, Inc., bisphenol A-type cyanate ester, bifunctional, functional group equivalent weight 139) (B)-3: Isocyanate group-containing compound (b3), Duranate TKA-100 (manufactured by Asahi Kasei Corporation, isocyanurate-type isocyanate compound, trifunctional, functional group equivalent: 180 g / eq.) (B)-4: Metal chelate compound (b4), Orgatix ZC-150 (manufactured by Matsumoto Fine Chemical Co., Ltd., organic zirconia compound, tetrafunctional, functional group equivalent weight 122 g / eq.) (B)-5: Carbodiimide group-containing compound (b5), Carbodilite V-05 (manufactured by Nisshinbo Chemical Co., Ltd., carbodiimide group-containing compound, trifunctional or higher, functional group equivalent: 262 g / eq.) (B)-6: Maleimide group-containing compound (b6): BMI-3000 (manufactured by Daiwa Chemical Industry Co., Ltd., bisphenol A diphenyl ether bismaleimide, bifunctional, functional group equivalent weight 285.3 g / eq.) (B)-7: (b7): N-12 (dodecanedioic acid dihydrazide)
[0139] (Ultraviolet absorber (C)) (C)-1: Tinuvin 326 (BASF Japan, benzotriazole-containing compound) (Filler (D)) (D)-1: SC2050-MB (manufactured by Admatechs Co., Ltd., silica, average particle size D 50 ;0.5μm) (D)-2: SP-2 (manufactured by Denka Co., Ltd., boron nitride, average particle diameter D 50 ;4.0μm) (D)-3: Exolit OP935 (Clariant, aluminum phosphinate, average particle size D 50 ;2.5μm) (D)-4: KT-300 (Kitamura Co., Ltd., fluorine-based filler, average particle diameter D 50 ;10.0μm) (D)-5: E101-S (Sumitomo Chemical Co., Ltd., liquid crystal polymer, average particle size D 50 ;17.5μm)
[0140] [Example 1] <<Production of coating liquid>> A container was charged with 100 parts of the polyimide resin (P1) of Synthesis Example 1, 5 parts of the crosslinking agent ((B)-1), 7.0 parts of the ultraviolet absorber (C)-1 (5.0% by mass relative to the nonvolatile content), and 28.0 parts of the filler (D)-1 (20.0% by mass relative to the nonvolatile content) in terms of solid content, and a mixed solvent (toluene:MEK=9:1 (mass ratio)) was added so that the nonvolatile content concentration was 30%, and the mixture was stirred for 10 minutes with a disper to obtain a coating solution.
[0141] <<Adhesive sheet manufacturing>> The resulting coating solution was uniformly coated using a doctor blade onto a 50 μm-thick heavy release film (a polyethylene terephthalate (PET) film coated with a heavy release agent) so that the dried thickness was 25 μm, and then dried at 100°C for 2 minutes. The coating was then cooled to room temperature to obtain an adhesive sheet with a single-sided release film. The adhesive sheet side of the resulting adhesive resin sheet with a single-sided release film was then superimposed on a 50 μm-thick light release film (a polyethylene terephthalate (PET) film coated with a light release agent), to obtain an adhesive sheet with double-sided release films consisting of a heavy release film / adhesive sheet / light release film. The evaluations described below were then carried out. The results are shown in Table 3.
[0142] [Examples 2 to 55, Comparative Examples 1 to 8] Coating solutions according to Examples 2 to 55 and Comparative Examples 1 to 8 were prepared and adhesive sheets with double-sided release films were obtained in the same manner as in Example 1, except that the ingredients and amounts were changed as shown in Tables 3 to 7. The evaluation results are also shown in Tables 3 to 7.
[0143] α. Lamination with LCP substrate The light-release film was peeled off from the adhesive sheet with double-sided release film, and the exposed adhesive sheet surface was bonded to the LCP side of a single-sided copper-clad laminate (Vextar (registered trademark) FCCL Fxx-05012, manufactured by Kuraray Co., Ltd.) consisting of a 50 μm LCP film and a 12 μm copper foil using a vacuum laminator (Nikko Materials Co., Ltd., small pressure vacuum laminator V-130). The vacuum lamination conditions were a heating temperature of 90°C, a vacuum time of 60 seconds, a vacuum ultimate pressure of 2 hPa, a pressure of 0.4 MPa, and a pressure time of 60 seconds. Next, the heavy release film was peeled off, and the copper foil side of a second single-sided copper-clad laminate was similarly bonded to the exposed adhesive sheet surface using a vacuum laminator to produce evaluation sample α with a laminate structure of copper foil / LCP film / adhesive sheet / LCP film / copper foil.
[0144] A test piece 100 mm wide and 100 mm long was cut out from the evaluation sample α and stored in an atmosphere of 23°C and 50% relative humidity for 24 hours or more. Then, a 90° peel test was performed in an atmosphere of 23°C and 50% relative humidity at a pulling rate of 50 mm / min to measure the adhesive strength (N / cm). A: 2N / cm or more. An extremely good result. B: 1N / cm or more and less than 2N / cm. Good result. C: 0.5 N / cm or more and less than 1 N / cm. This is within the practical range. D: Less than 0.5 N / cm. Not practical.
[0145] β. Plating solution resistance of the cured product The plating solution resistance of the cured product was evaluated by the appearance after plating tests I and II described below were performed on each test piece. [I. Acid Plating Test] The adhesive sheet with double-sided release film was cut to a size of 65 mm x 65 mm, and the light release film was peeled off. The adhesive sheet surface exposed by the peeling was then laminated at 90°C with the copper surface of a two-layer CCL [ESPANEX MC18-25-00FRM] manufactured by Nippon Steel & Sumikin Chemical Co., Ltd., followed by a 60-minute pressure bonding treatment at 180°C and 2.0 MPa. Finally, the heavy release film was peeled off to prepare a test piece for evaluation. The light release film was peeled off from the adhesive sheet with double-sided release film, and the exposed adhesive sheet surface was subjected to an electroless nickel treatment according to the procedures and conditions a to g below. a. Acidic degreasing process: Immerse in ICP Clean S-135K (manufactured by Okuno Pharmaceutical Industries Co., Ltd.) at 40°C for 4 minutes. b. Soft etching process: Immersion in sodium persulfate at 30°C for 1 minute. c. Desmutting process: Immerse in sulfuric acid at 25°C for 1 minute. d. Pre-dip process: Immerse in hydrochloric acid at 25°C for 30 seconds. e. Activation step: Immerse in ICP Accela (manufactured by Okuno Pharmaceutical Industries Co., Ltd.) at 30°C for 1 minute. f. Post-dipping step: Immerse in sulfuric acid at 25°C for 1 minute. g. Electroless nickel plating process: Immersed in IP Nicoron FPF (manufactured by Okuno Pharmaceutical Industries Co., Ltd.) at 85°C for 20 minutes. [II. Alkaline Plating Test] Test pieces for evaluation were prepared in the same manner as in the acid plating test, and electroless nickel treatment was carried out on these test pieces according to the following procedures and conditions s to w. s. Alkaline degreasing step: Immersion in an alkaline degreasing agent (50 g / L aqueous solution of Ace Clean A-220 (trade name) manufactured by Okuno Pharmaceutical Industries Co., Ltd.) at 50°C for 5 minutes. t. Etching treatment step: Immersion in an aqueous solution containing 400 g / L of chromic anhydride and 400 g / L of 98% sulfuric acid at 67°C for 10 minutes. u. Activation step: Immerse in an aqueous solution containing 20 mL / L of 98% sulfuric acid at 25°C for 2 minutes. v. Catalytic activation: Immersed in a catalyst activation solution (aqueous solution containing 10 mL / L of TSP Activator Concentrate (trademark) manufactured by Okuno Chemical Industries Co., Ltd.) at 25°C for 2 minutes. w. Electroless nickel plating process: Immersion in an ammonia-alkali type autocatalytic electroless nickel plating solution (a pH 9 aqueous solution containing 160 mL / L of Chemical Nickel A (trade name) and 160 mL / L of Chemical Nickel B (trade name) manufactured by Okuno Pharmaceutical Industries Co., Ltd.) at 40°C for 5 minutes.
[0146] The appearance of the evaluation test piece that had been treated in I was visually inspected to check for any abnormalities such as swelling or peeling of the adhesive layer after curing. If no abnormalities were found, step I was repeated three more times. The evaluation test piece in II was also tested in the same manner. This test was conducted to evaluate the resistance of the hardened layer to the plating solution by appearance, and the resistance was evaluated based on the number of times steps a to g were repeated. A: For both test pieces I and II, there was no visible defect even after the third immersion. Very good. B: For both test pieces I and II, there was no appearance defect until the second immersion, but after the third immersion, appearance defect occurred in one of the test pieces. Good. C: For both test pieces I and II, there was no visual defect until the first immersion, but after the second immersion, visual defects occurred in one of the test pieces. This does not pose a problem in practical use. D: Either I or II test piece had a poor appearance after the first immersion. Unsuitable for practical use.
[0147] γ. Insulation reliability after heat cycle test of cured material The evaluation method will be explained with reference to Figures 1 to 4. A laminate of 12 μm thick copper foil and 25 μm thick polyimide film was etched, and a cathode electrode comb-shaped signal wiring 2 having cathode electrode connection points 2' and an anode electrode comb-shaped signal wiring 3 having anode electrode connection points 3' were formed on the polyimide film 1 (see Figure 1). The line / space was 0.05 mm / 0.05 mm. Next, the light-release film of the adhesive sheet with double-sided release film was peeled off and the adhesive sheet surface was attached to the surface on which the cathode electrode comb-shaped signal wiring 2 and the anode electrode comb-shaped signal wiring 3 were formed. At this time, the vicinity of the cathode electrode connection point 2' and the vicinity of the anode electrode connection point 3' were exposed. The sheets were then bonded using a vacuum laminator. The heavy-release film was then peeled off to expose the adhesive sheet 4 (see Figure 2). A single-sided copper-clad laminate (MC18-25-00FRM) 5, which had a two-layer structure consisting of an insulating layer 5b and a copper layer 5a, was then bonded to the adhesive sheet 4 using a vacuum laminator so that the insulating layer 5b contacted the adhesive sheet 4. The laminate was then thermally cured in a heat press at 180°C for 1 hour at 2 MPa to form a cured layer 4' of the adhesive sheet 4, yielding a laminate γ for evaluation (see Figures 3 and 4).
[0148] Next, the evaluation laminate γ was subjected to a heat cycle treatment. The evaluation laminate γ was placed in a thermal shock device ("TSE-11-A", manufactured by Espec Corporation) and subjected to 200 cycles of alternating exposure conditions: high temperature exposure at 125°C for 15 minutes and low temperature exposure at -50°C for 15 minutes.
[0149] The removed evaluation laminate γ was then placed in an atmosphere of 85°C and 85% RH (relative humidity), with an anode electrode connected to anode electrode connection point 3' and a cathode electrode connected to cathode electrode connection point 2', and a voltage of 50 V was applied for 1000 hours. The change in resistance was then continuously measured until 1000 hours had passed. "Leak touch" refers to a momentary drop in resistance and current flow caused by insulation breakdown due to a short circuit. If there is no leak touch, there is no deterioration in insulation. The evaluation criteria are as follows. A: Resistance after 1000 hours is 1 x 10 10 Over Ω and no leak touch. Extremely good. B: Resistance after 1000 hours is 1 x 10 8 Ω or more, 1×10 10 Less than Ω and no leak touch. Good. C: Not applicable to A or B, resistance value after 1000 hours is 1 x 10 7 Ω or more and leak touch less than one time. No practical problems. D: Does not fall under A to C. Not practical.
[0150] δ. Laser processability of hardened layer A method for evaluating the laser processability of the cured layer of an adhesive sheet will be described with reference to Figure 5. The light release film was peeled off from an adhesive sheet with double-sided release film, and the four exposed surfaces of the adhesive sheet were bonded to the copper foil 11 on one side of a double-sided copper-clad laminate 10, which consisted of a 50 μm polyimide film 12 with 12 μm copper foil 11 laminated on both sides. Next, the heavy release film was peeled off, and the polyimide film 22 side of a single-sided copper-clad laminate 20, which consisted of a 50 μm polyimide film 22 and a 12 μm copper foil 21 laminated on both sides, was similarly bonded to the four exposed surfaces of the adhesive sheet using a vacuum laminator. The laminate was then thermally cured in a heat press at 180°C for 1 hour at 2 MPa, yielding an evaluation sample δ having a laminate structure of copper foil 11 / polyimide film 12 / copper foil 11 / cured layer 4' of adhesive sheet / polyimide film 22 / copper foil 21.
[0151] Evaluation sample δ was irradiated with a UV-YAG laser (Model 5330, manufactured by ESI) from the copper foil 21 side of single-sided copper-clad laminate 20, and a blind via with a diameter of 150 μm was drilled up to the boundary between the cured layer 4' of the adhesive sheet and the double-sided copper-clad laminate 10 (see Figure 5). Next, the cross section of the blind via portion 30 was observed with a laser microscope (Keyence VK-X100) at a magnification of approximately 20 to 500 times, and the maximum length of side etching 31 (horizontal etching exceeding the designed opening diameter) occurring in the cured layer 4' of the thermosetting adhesive sheet was measured. The evaluation criteria were as follows: A: 5 μm or less. An extremely good result. B: Greater than 5 μm and equal to or less than 7 μm. Good results. C: More than 7 μm and less than 10 μm. This is within the practical range. D: Larger than 10 μm. Not practical.
[0152] [Table 3]
[0153] [Table 4]
[0154] [Table 5]
[0155] [Table 6]
[0156] [Table 7]
[0157] The compositions using polyimide resins having no phenolic hydroxyl groups were inferior in plating solution resistance as shown in Comparative Examples 1 and 2. In addition, the residues X derived from dimer diamine and / or dimer diisocyanate were 2 Comparative Example 3, which used a polyimide resin not having d, was inferior in lamination properties to an LCP substrate. 7 Comparative Example 4, which used a polyimide resin whose Pa temperature exceeded 90°C, also had poor lamination properties to LCP substrates. Furthermore, Comparative Examples 5 to 8, in which the amount of crosslinking agent (B) was outside the range of 0.5 to 30 parts by mass per 100 parts by mass of polyimide resin (A), were poor in migration resistance and other properties after heat cycle testing. On the other hand, Examples 1 to 52 according to the present invention were confirmed to have excellent lamination properties to LCP substrates even at low temperatures and for short periods of time. Furthermore, it was confirmed that the cured products had excellent alkali resistance and acid resistance, as well as excellent insulation reliability after heat cycle testing. [Explanation of symbols]
[0158] 1 Polyimide film 2. Comb-shaped signal wiring for cathode electrode 2' Cathode electrode connection point 3. Comb-shaped signal wiring for anode electrode 3' Anode electrode connection point 4 adhesive sheets 4' hardened layer 5 Single-sided copper-clad laminate 5a copper layer 5b Insulating layer 10 Double-sided copper-clad laminate 11 Copper foil 12 Polyimide film 20 Single-sided copper-clad laminate 21 Copper foil 22 Polyimide film 30 Blind via section 31 Side Etching
Claims
1. A thermosetting composition comprising a polyimide resin (A) and a crosslinking agent (B) having two or more functional groups, The polyimide resin (A) is represented by the general formula (1): [Formula 1] (X 1 is independently a tetravalent tetracarboxylic acid residue for each repeating unit, and X 2 is a divalent organic group for each repeating unit, 1 and imide bonds are bonded together to form two imide rings.) and having a phenolic hydroxyl group in at least one of a side chain, a side group and a molecular chain terminal, The X 2 At least a portion of the residue X is derived from dimer diamine and / or dimer diisocyanate. 2 d, The polyimide resin (A) has a storage modulus G′ of 1.0×10 7 The temperature at which the pressure drops to Pa is between 30 and 90°C. The crosslinking agent (B) includes one or more compounds selected from the group consisting of an epoxy group-containing compound (b1), a cyanate ester compound (b2), an isocyanate group-containing compound (b3), a metal chelate compound (b4), a carbodiimide group-containing compound (b5), and a maleimide group-containing compound (b6); the total content of the epoxy group-containing compound (b1), the cyanate ester compound (b2), the isocyanate group-containing compound (b3), the metal chelate compound (b4), the carbodiimide group-containing compound (b5) and the maleimide group-containing compound (b6) is 0.5 to 10 parts by mass per 100 parts by mass of the polyimide resin (A); A thermosetting composition, wherein the polyimide resin (A) has a weight average molecular weight of 15,000 to 100,000.
2. 2. The thermosetting composition according to claim 1, which has a glass transition temperature of 0 to 70° C. after being heat-cured at 180° C. for 60 minutes.
3. 3. The thermosetting composition according to claim 1, wherein the phenolic hydroxyl group satisfies at least any one of the following (i) to (iv): (i) It has a phenolic hydroxyl group at the molecular chain terminal, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the meta or ortho position of the aromatic ring having the phenolic hydroxyl group. (ii) It has a phenolic hydroxyl group at the molecular chain terminal, and an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom forming an imide ring derived from a monoamine is bonded to the aliphatic group. (iii) the X 2 A part of the diamine residue X having a phenolic hydroxyl group 2 f, and a nitrogen atom forming an imide ring derived from a diamine is bonded to the aromatic ring having the phenolic hydroxyl group. (iv) the X 2 A part of the diamine residue X having a phenolic hydroxyl group 2 f, which has an aliphatic group directly bonded to the aromatic ring having the phenolic hydroxyl group, and a nitrogen atom forming an imide ring derived from a diamine is bonded to the aliphatic group.
4. The X in the polyimide resin (A) 1 At least a part of X has an aliphatic group 1 4. The thermosetting composition according to claim 1, wherein a is a.
5. 5. The thermosetting composition according to claim 1, further comprising an ultraviolet absorber (C) in an amount of 0.1 to 10 mass% relative to 100 mass% of the nonvolatile content.
6. 6. The thermosetting composition according to claim 1, further comprising 3 to 60 mass% of a filler (D) relative to 100 mass% of nonvolatile matter.
7. The thermosetting composition according to any one of claims 1 to 6, wherein the polyimide resin (A) optionally has at least one of an amino group and an acid anhydride group, and [phenolic hydroxyl value] / [amino group value + acid anhydride group value + phenolic hydroxyl value] is 40.0 to 100.
8. A thermosetting composition according to any one of claims 1 to 7, wherein the polyimide resin (A) has 50 to 100 mol % of phenolic hydroxyl groups at its molecular chain terminals relative to 100 mol % of functional groups at its molecular chain terminals.
9. The thermosetting resin composition according to any one of claims 1 to 8, wherein the polyimide resin (A) has a phenolic hydroxyl value of 1 to 20 mg KOH / g.
10. An adhesive sheet comprising the thermosetting composition according to any one of claims 1 to 9.
11. A printed wiring board formed using the adhesive sheet according to claim 10.
12. An electronic device comprising the printed wiring board according to claim 11.
